HOT-DIP Al-Zn-Si-Mg-PLATED STEEL SHEET, SURFACE-TREATED STEEL SHEET, AND COATED STEEL SHEET
Patent Information
- Application Number
- JP2023125062
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2043-07-31
AI Technical Summary
【0015】 本発明によれば、ドロス欠陥等の他の欠陥がなく、しわ状欠陥の発生が抑制され、優れた表面外観を有する溶融Al-Zn-Si-Mg系めっき鋼板を提供することが可能となる。 また、本発明によれば、優れた表面外観及び耐白錆性を有する表面処理鋼板、並びに、優れた表面外観及び耐食性に優れた塗装鋼鈑を提供することが可能となる。
Smart Images

Figure 2025021252000001 
Figure 2025021252000002 
Figure 2025021252000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a hot-dip Al-Zn-Si-Mg plated steel sheet, a surface-treated steel sheet and a coated steel sheet having excellent surface appearance. [Background technology]
[0002] Hot-dip Al-Zn-plated steel sheets, typified by 55% Al-Zn, are known to exhibit high corrosion resistance among various plated steel sheets because they combine the sacrificial corrosion protection of Zn with the high corrosion resistance of Al, as shown in, for example, Patent Document 1. For this reason, hot-dip Al-Zn-plated steel sheets are used mainly in the field of building materials such as roofs and walls that are exposed to the outdoors for long periods of time, and in the field of civil engineering and construction such as guardrails, wiring and piping, and soundproof walls, due to their excellent corrosion resistance. In particular, the demand for hot-dip Al-Zn coated steel sheets has been increasing in recent years due to the growing demand for materials with excellent corrosion resistance and maintenance-free materials in more severe environments, such as acid rain caused by air pollution, the spraying of de-icing agents to prevent roads from freezing in snowy areas, and coastal area development.
[0003] The coating of hot-dip Al-Zn coated steel sheets is composed of α-Al phases, which are areas where Al containing supersaturated Zn has solidified in the form of dendrites, and Zn-Al eutectic structures that exist in the gaps between dendrites (interdendritic), and is characterized by a structure in which the α-Al phases are layered in the thickness direction of the coating. This characteristic coating structure makes the corrosion progression path from the surface complex, making it difficult for corrosion to progress easily, and it is also known that hot-dip Al-Zn coated steel sheets can achieve superior corrosion resistance compared to hot-dip galvanized steel sheets with the same coating thickness.
[0004] Attempts have been made to further extend the life of hot-dip Al-Zn-plated steel sheets, and hot-dip Al-Zn-Si-Mg-plated steel sheets to which Mg has been added are known. As such a hot-dip Al-Zn-Si-Mg-plated steel sheet, for example, Patent Document 1 discloses a hot-dip Al-Zn-Si-Mg-plated steel sheet that contains an Al-Zn-Si alloy containing Mg in a plating film, the Al-Zn-Si alloy being an alloy containing 45 to 60 wt % of elemental aluminum, 37 to 46 wt % of elemental zinc, and 1.2 to 2.3 wt % of Si, and the concentration of the Mg is 1 to 5 wt %. Furthermore, Patent Document 2 discloses a hot-dip Al-Zn-Si-Mg plated steel sheet in which the plating film contains one or more of 2 to 10 mass % Mg and 0.01 to 10 mass % Ca, thereby improving corrosion resistance and enhancing protective action after the base steel sheet is exposed. Furthermore, Patent Document 3 discloses a hot-dip Al-Zn-Si-Mg plated steel sheet in which a coating layer is formed containing, by mass%, 1 to 15% Mg, 2 to 15% Si, 11 to 25% Zn, with the remainder being Al and unavoidable impurities, and the size of intermetallic compounds such as Mg2Si phase and MgZn2 phase present in the plating film is set to 10 μm or less, thereby improving the corrosion resistance of the flat plate and end faces.
[0005] However, hot-dip Al-Zn-Si-Mg-plated steel sheets have a problem in that the surface appearance is significantly deteriorated due to the occurrence of wrinkle-like irregular defects, which will be described later. When Mg is added to a molten Al-Zn-Si bath and a steel sheet is plated, Mg is an element that oxidizes more easily than other plating constituent elements, so during the cooling and solidification process of the plating film, Mg reacts with oxygen in the outermost layer that comes into contact with the air to produce Mg-based oxides. As a result, the Mg concentration in the vicinity of the outermost layer decreases, and to compensate for this, Mg gradually diffuses from the inside of the plating film to the outermost layer. As a result, a thick layer of Mg-based oxide is formed in the outermost layer before the plating film completely solidifies to the inside, and a difference in fluidity occurs between the inside of the plating film, which is prone to flow before solidification, and the Mg-based oxide layer. As a result, the Mg-based oxide layer cannot keep up with the flow inside the plating film, and wrinkle-like uneven defects (wrinkle-like defects) occur on the plating surface of the hot-dip Al-Zn-Si-Mg-plated steel sheet that is produced. Therefore, there has been a demand for the development of a technology to improve wrinkle defects in hot-dip Al-Zn-Si-Mg coated steel sheets.
[0006] Patent Documents 4 and 5 disclose techniques for suppressing the oxidation of Mg in the plating surface layer and suppressing the occurrence of wrinkle defects by including Sr in the plating film. These techniques utilize the phenomenon that Sr is oxidized preferentially over Mg in the unsolidified plating layer surface layer coming out of the plating bath.
[0007] Furthermore, the above-mentioned hot-dip Al-Zn-Si-Mg-plated steel sheets have a problem in that, when used in a severely corrosive environment, the plating film corrodes and white rust occurs. Since this white rust deteriorates the appearance of the steel sheet, plated steel sheets with improved white rust resistance are being developed. Therefore, Patent Documents 6 and 7 disclose surface-treated steel sheets in which a chemical conversion coating containing a urethane resin is formed on the plating coating of a hot-dip Al-Zn-Si-Mg-plated steel sheet, thereby improving the white rust resistance. However, even in the case of surface-treated steel sheets as disclosed in Patent Documents 6 and 7, the steel sheets are affected by the underlying hot-dip Al-Zn-Si-Mg-plated steel sheet, and therefore, there is still a need to improve the deterioration of surface appearance caused by the occurrence of the above-mentioned wrinkle defects.
[0008] Furthermore, the above-mentioned hot-dip Al-Zn-Si-Mg-plated steel sheet may be used as a painted steel sheet having a chemical conversion coating or a primer coating formed on the surface and various other coating films formed thereon. Such coated steel sheets are subjected to various processes, including 90-degree or 180-degree bending by press forming, roll forming, or embossing, and are required to have coating film durability over a long period of use. To meet these requirements, it has been common to apply a chromate-containing chemical conversion treatment to hot-dip Al-Zn-plated steel sheets, incorporate a chromate-based rust-preventive pigment in the primer coating, and then coat the primer coating with a thermosetting polyester resin coating or, for those who require higher weather resistance, a fluororesin coating. However, in recent years, the use of chromate, an environmentally harmful substance, in such coated steel sheets has come to be viewed as problematic, and there is a strong demand for chromate-free coated steel sheets that do not contain chromate. For example, a chromate-free coated steel sheet as disclosed in Patent Document 8 has been proposed. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Patent No. 5020228 [Patent Document 2] Patent No. 5000039 [Patent Document 3] JP 2002-12959 A [Patent Document 4] JP 2000-328214 A [Patent Document 5] International Publication No. 2020 / 179147 [Patent Document 6] JP 2019-155872 A [Patent Document 7] JP 2021-181214 A [Patent Document 8] JP 2005-169765 A Summary of the Invention [Problem to be solved by the invention]
[0010] However, in any of the techniques disclosed in the documents, it is difficult to suppress the occurrence of the wrinkle defects described above without deteriorating other physical properties. The techniques disclosed in Patent Documents 4 and 5 have a problem that, during the production of a hot-dip Al-Zn-Si-Mg-plated steel sheet in which Sr is added to the plating film, the surface of the plating bath to which Sr is added is easily oxidized, and the generated oxide-based dross adheres to the plating film to cause new dross defects, which deteriorate the surface appearance.
[0011] In addition, although the techniques of Patent Documents 6 and 7 can improve white rust resistance, even in the case of surface-treated steel sheets, they are affected by the underlying hot-dip Al-Zn-Si-Mg-plated steel sheet, and the deterioration of surface appearance due to the occurrence of wrinkle-like defects is still desired to be improved. Furthermore, with regard to the technology of Patent Document 8, the surface appearance of a coated steel sheet, particularly its image clarity, is obviously affected by the surface shape of the plated steel sheet that serves as the base, and the height difference of the unevenness caused by the occurrence of the above-mentioned wrinkle-like defects and dross defects reaches several tens of μm, so even if the surface is smoothed by a coating film, the unevenness is not completely eliminated, and improvement of the surface appearance of the coated steel sheet remains an issue. In addition, since the coating film formed on the convex parts of the plating film has a thin film thickness, there is a concern that the corrosion resistance may be locally reduced, and therefore it has been desired to improve the surface appearance of the plated steel sheet that serves as the base, particularly the surface shape.
[0012] In view of the above circumstances, an object of the present invention is to provide a hot-dip Al-Zn-Si-Mg coated steel sheet which is free from other defects such as dross defects, suppresses the occurrence of wrinkle-like defects, and has an excellent surface appearance. Another object of the present invention is to provide a surface-treated steel sheet having an excellent surface appearance and white rust resistance, and a coated steel sheet having an excellent surface appearance and excellent corrosion resistance. [Means for solving the problem]
[0013] As a result of investigations aimed at solving the above-mentioned problems, the present inventors have noticed that wrinkle-like defects can be suppressed without causing dross defects and the like by adding Mn to the plating film of a hot-dip Al-Zn-Si-Mg-plated steel sheet, and have found that the occurrence of wrinkle-like defects can be suppressed by adjusting the amount of Mn added and minimizing the height difference on the steel sheet surface (plating film surface).
[0014] The present invention has been made based on the above findings, and the gist of the present invention is as follows. 1. A hot-dip Al-Zn-Si-Mg-based plated steel sheet having a plating film, The plating film has a composition containing 45 to 65 mass% Al, 1.0 to 3.0 mass% Si, 1.0 to 10.0 mass% Mg, and 0.01 to 0.5 mass% Mn, with the remainder being Zn and unavoidable impurities; A hot-dip Al-Zn-Si-Mg plated steel sheet, characterized in that the height difference of the steel sheet surface per mm of length is 10 μm or less in an area excluding 50 mm from both ends of the steel sheet. 2. The hot-dip Al-Zn-Si-Mg plated steel sheet according to item 1 above, characterized in that the plated film has a Mn content of 0.1 to 0.3 mass %. 3. The hot-dip Al-Zn-Si-Mg plated steel sheet according to 1 or 2 above, characterized in that an alloy layer containing Mn is provided at the interface between the plated film and a base steel sheet. 4. The hot-dip Al-Zn-Si-Mg plated steel sheet according to any one of 1 to 3 above, characterized in that the plated film further contains 0.01 to 3.0 mass% in total of one or more elements selected from B, Ca, Ti, V, Cr, Sr, Mo, In, Sn, Sb, Ce, and Bi. 5. A surface-treated steel sheet comprising the plating film according to any one of 1 to 4 above and a chemical conversion film formed on the plating film, The chemical conversion coating film is a surface-treated steel sheet characterized in that it contains at least one resin selected from the group consisting of epoxy resins, urethane resins, acrylic resins, acrylic silicone resins, alkyd resins, polyester resins, polyalkylene resins, amino resins, and fluororesins, and at least one metal compound selected from the group consisting of P compounds, Si compounds, Co compounds, Ni compounds, Zn compounds, Al compounds, Mg compounds, V compounds, Mo compounds, Zr compounds, Ti compounds, and Ca compounds. 6. A coated steel sheet having a coating film formed directly or via a chemical conversion coating on the plating film according to any one of 1 to 4 above, The chemical conversion coating contains a resin component containing 30 to 50 mass% in total of (a): an anionic polyurethane resin having an ester bond and (b): an epoxy resin having a bisphenol skeleton, the content ratio of (a) to (b) ((a):(b)) being in the range of 3:97 to 60:40 in terms of mass ratio, and an inorganic compound containing 2 to 10 mass% of a vanadium compound, 40 to 60 mass% of a zirconium compound, and 0.5 to 5 mass% of a fluorine compound; The coating film has at least a primer coating film, and the primer coating film contains a polyester resin having a urethane bond, and an inorganic compound including a vanadium compound, a phosphate compound, and magnesium oxide. Effect of the Invention
[0015] According to the present invention, it is possible to provide a hot-dip Al-Zn-Si-Mg-plated steel sheet which is free from other defects such as dross defects, suppresses the occurrence of wrinkle-like defects, and has an excellent surface appearance. Furthermore, according to the present invention, it is possible to provide a surface-treated steel sheet having an excellent surface appearance and white rust resistance, and a coated steel sheet having an excellent surface appearance and excellent corrosion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] <Hot-dip Al-Zn-Si-Mg coated steel sheet> The hot-dip Al-Zn-Si-Mg plated steel sheet of the present invention has a plating film on the surface of the steel sheet. The plating film has a composition containing 45 to 65 mass % Al, 1.0 to 3.0 mass % Si, 1.0 to 10.0 mass % Mg, and 0.01 to 0.5 mass % Mn, with the remainder being Zn and unavoidable impurities.
[0017] The Al content in the plating film is 45 to 65 mass %, and preferably 50 to 60 mass %, in view of the balance between corrosion resistance and operability. This is because, if the Al content in the plating film is at least 45% by mass, dendritic solidification of Al occurs, and a plating film structure mainly composed of a dendritic solidification structure of the α-Al phase can be obtained. The dendritic solidification structure is laminated in the thickness direction of the plating film, which complicates the corrosion progression path and improves the corrosion resistance of the plating film itself. In addition, the more the α-Al phase dendrite parts are laminated, the more complex the corrosion progression path becomes, and the more difficult it is for corrosion to reach the base steel sheet, thereby improving the corrosion resistance, so it is preferable that the Al content is 50% by mass or more. On the other hand, if the Al content in the plating film exceeds 65% by mass, most of the Zn changes to a structure in which it is solid-dissolved in α-Al, and the dissolution reaction of the α-Al phase cannot be suppressed, which may deteriorate the corrosion resistance of the hot-dip Al-Zn-Si-Mg-plated steel sheet. For this reason, the Al content in the plating film must be 65% by mass or less, and is preferably 60% by mass or less.
[0018] The Si in the plating film is added mainly for the purpose of suppressing the growth of an Fe-Al and / or Fe-Al-Si interfacial alloy layer formed at the interface with the base steel sheet and preventing deterioration of the adhesion between the plating film and the steel sheet. In fact, when a steel sheet is immersed in an Al-Zn plating bath containing Si, an alloying reaction occurs between the Fe on the steel sheet surface and the Al and Si in the bath, and an Fe-Al and / or Fe-Al-Si intermetallic compound layer is formed at the interface between the base steel sheet and the plating film. At this time, the growth rate of the Fe-Al-Si alloy is slower than that of the Fe-Al alloy, so the higher the ratio of the Fe-Al-Si alloy, the more the growth of the entire interfacial alloy layer is suppressed. Therefore, the Si content in the plating film must be 1.0 mass% or more. On the other hand, if the Si content in the plating film exceeds 4.0 mass%, not only will the aforementioned effect of inhibiting the growth of the interface alloy layer saturate, but the presence of excess Si phase in the plating film will also promote corrosion, so the Si content in the plating film is set to 4.0 mass% or less. In addition, from the viewpoint of inhibiting the presence of excess Si phase, the Si content in the plating film is preferably set to 3.0 mass% or less.
[0019] The plating film contains 1.0 to 10.0 mass % of Mg. By including Mg in the plating film, the above-mentioned Si can be present in the form of an intermetallic compound of Mg2Si phase, and the promotion of corrosion can be suppressed. Furthermore, when the plating film contains Mg, the MgZn2 phase, which is an intermetallic compound, is also formed in the plating film, which has the effect of further improving corrosion resistance. If the Mg content in the plating film is less than 1.0 mass%, Mg is used to dissolve in the α-Al phase, which is the main phase, rather than to form the intermetallic compounds (Mg2Si, MgZn2), and sufficient corrosion resistance cannot be ensured. On the other hand, if the Mg content in the plating film is high, the effect of improving corrosion resistance is saturated, and in addition, the α-Al phase becomes brittle, which reduces workability, so the content is set to 10.0 mass% or less. Furthermore, the Mg content in the plating film is preferably 5.0 mass % or less from the viewpoints of suppressing the generation of dross during plating formation, facilitating plating bath management, and further improving the surface appearance.
[0020] In the hot-dip Al-Zn-Si-Mg steel sheet of the present invention, the plating film contains 0.01 to 0.5 mass% of Mn. When the plating film contains 0.01 mass% or more of Mn, a needle-shaped and / or chunky Mn-Fe-based interfacial alloy layer is formed between the plating film and the base steel, and the alloy layer has an anchor effect that suppresses the movement of the plating solution film while the plating is completely solidified, thereby suppressing the occurrence of wrinkle-like defects caused by Mg-based oxides formed on the surface of the plating film. On the other hand, if the Mn content in the plating film exceeds 0.5 mass%, the melting point of the plating bath increases, and plating treatment must be performed at a high bath temperature, which causes abnormal growth of the interfacial alloy layer formed between the plating film and the base steel, deteriorating workability, increasing the amount of dross generated, and deteriorating the plating appearance, particularly the surface shape. If the Mn content in the plating film is 0.5 mass% or less, the amount of dross generated in the plating bath is the same as when no Mn is added, so the occurrence of dross defects can be suppressed and a stable excellent surface appearance can be obtained. Therefore, the Mn content in the plating film is set to 0.01 to 0.5 mass %. From the same viewpoint, the Mn content in the plating film is preferably 0.1 to 0.3 mass %.
[0021] From the viewpoint of a balance between the effect of improving corrosion resistance, the effect of suppressing wrinkle defects, and the effect of suppressing dross defects, the content of Mg and Mn in the plating film is preferably such that the ratio of the Mn content to the Mg content (Mn / Mg) is, in mass ratio, 0.02 or more (Mn / Mg≧0.02). From the same viewpoint, the ratio of the Mn content to the Mg content (Mn / Mg) is more preferably 0.03 or more (Mn / Mg≧0.03).
[0022] The plating film contains Zn and unavoidable impurities in addition to the above-mentioned Al, Si, Mg, and Mn. Among these, the inevitable impurities include Fe. This Fe is inevitably contained in the plating film as a result of dissolution of the steel sheet or bath-immersed equipment into the plating bath, and as a result of being supplied by diffusion from the base steel sheet during the formation of the interface alloy layer. The Fe content in the plating film is usually about 0.3 to 2.0 mass%. Other inevitable impurities include Ni, Cu, etc. The total content of the unavoidable impurities is not particularly limited, but if contained in excess, various properties of the plated steel sheet may be adversely affected, so the total content is preferably 5.0 mass % or less.
[0023] In addition, the plating film preferably further contains, as necessary, one or more elements selected from B, Ca, Ti, V, Cr, Sr, Mo, In, Sn, Sb, Ce, and Bi in a total amount of 0.1 to 3 mass %. These elements can improve the stability of the corrosion product when the plating film corrodes, thereby delaying the progress of corrosion, and can stabilize the spangle size on the plating surface, thereby improving the surface appearance.
[0024] The composition of the plating film can be confirmed, for example, by immersing the plating film in hydrochloric acid or the like to dissolve it, and subjecting the solution to ICP emission spectrometry, atomic absorption spectrometry, etc. This method is merely one example, and any method that can accurately quantify the composition of the plating film may be used, and is not particularly limited. Moreover, the coating film of the hot-dip Al-Zn-Si-Mg-plated steel sheet obtained by the present invention has a composition generally equivalent to that of the coating bath, and therefore the composition of the coating film can be controlled with high precision by controlling the composition of the coating bath.
[0025] The hot-dip Al-Zn-Si-Mg plated steel sheet of the present invention is characterized in that the difference in height of the coating surface per mm length is 10 μm or less in an area excluding 50 mm from both ends of the steel sheet surface. When the difference in height of the steel sheet surface, i.e., the plating film surface, is 10 μm or less, no wrinkle-like defects are present and an excellent surface appearance can be obtained. As described above, the wrinkle defect is a defect in which the surface of the plating film has a wrinkled uneven shape due to Mg-based oxides, and appears as a white streak pattern on the surface of the plating film. Therefore, suppressing the wrinkle defect means that the streak pattern is not visible. Therefore, by suppressing the height difference within a 1 mm long range on the steel sheet surface to within 10 μm, the streak pattern is not visible, and an excellent surface appearance can be obtained. From the same viewpoint, it is preferable that the height difference within a 1 mm long range on the steel sheet surface is within 5 μm. The steel sheet surface means the outermost surface of the steel sheet, and in the case of a hot-dip Al-Zn-Si-Mg-plated steel sheet, means the surface of the plating film. The height difference within a 1 mm length range of the steel sheet surface can be obtained, for example, by using a laser microscope to measure the height differences within a 1 mm range at any 100 points on the hot-dip Al-Zn-Si-Mg-plated steel sheet on which a plating film has been formed, and calculating the average of the measured values.
[0026] The reason for controlling the height difference of the steel sheet surface in the range excluding 50 mm from both ends of the steel sheet surface is that, in general, it is difficult to control the coating weight at both ends of a hot-dip galvanized steel sheet compared to the center of the steel sheet, and the cooling rate is also different, so wrinkle-like defects are likely to occur. In addition, such both ends of the steel sheet are often trimmed before use, so there is almost no problem with the surface appearance.
[0027] The method for controlling the height difference of the steel sheet surface per 1 mm of the plating film to 10 μm or less is not particularly limited other than the Mn content (0.01 to 0.5 mass%) in the plating film described above. For example, the height difference of the film surface can be suppressed by adjusting the content ratio of Mg and Mn in the plating film or by performing other surface treatment for suppressing the height difference.
[0028] In the hot-dip Al-Zn-Si-Mg-plated steel sheet of the present invention, an alloy layer containing Mn is preferably formed at the interface between the plating film and the base steel. The alloy layer is formed by an alloying reaction between Mn and Al, Fe, Si, etc. in the bath, and is mainly an Fe-Al-Mn or Fe-Al-Si-Mn intermetallic compound, and has an uneven shape in the plating surface direction, which can improve the adhesion between the plating film and the base steel sheet by an anchor effect. Furthermore, the anchor effect of the Mn-containing alloy layer appears at the time when the plating film solidifies, and the Mn-based interfacial alloy layer acts to minimize the movement of the plating solution film, so that it is also possible to suppress the occurrence of wrinkle-like defects.
[0029] In addition, in the hot-dip Al-Zn-Si-Mg plated steel sheet of the present invention, in order to impart excellent corrosion resistance, it is preferable that the diffraction intensities of Si and MgSi in the plated film, as determined by an X-ray diffraction method, satisfy the following relationship (1): Si (111) / Mg2Si (111)≦0.8 ···(1) Si (111): Diffraction intensity of the Si (111) plane (interplanar spacing d = 0.3135 nm), Mg2Si (111): Diffraction intensity of the Mg2Si (111) plane (interplanar spacing d = 0.3668 nm) As described above, in the present invention, it is preferable to control the abundance ratio of the Mg2Si phase and the Si phase that are generated in the plating film by the inclusion of Mg and Si to a specific ratio. Although the influence of these on the corrosion resistance is still under investigation and many points remain unclear, the following mechanism is presumed. When a hot-dip Al-Zn-Si-Mg-based plating film is exposed to a corrosive environment, the intermetallic compounds dissolve preferentially over the α-Al phase, resulting in a Mg-rich environment in the vicinity of the formed corrosion products. It is presumed that in such a Mg-rich environment, the formed corrosion products are less likely to decompose, and as a result, the protective effect of the plating film is enhanced. In addition, the protective effect of the plating film is more reliably expressed when the Si in the plating film exists as the Mg2Si phase rather than the Si phase, so it is considered effective to reduce the ratio of the Si phase to the Mg2Si phase.
[0030] The abundance ratio of Mg2Si and Si in the plating film preferably satisfies the relationship (1): Si (111) / Mg2Si (111)≦0.8 using the diffraction peak intensity obtained by X-ray diffraction. However, when the abundance ratio of Mg2Si and Si in the plating film does not satisfy the relationship (1), that is, Si (111) / Mg2Si (111)>0.8, the Si phase present in the plating film increases, and the above-mentioned Mg-rich environment cannot be obtained in the vicinity of the corrosion product, making it difficult to obtain the protective effect of the plating film. From the same viewpoint, the abundance ratio of Si to Mg2Si (Si (111) / Mg2Si (111)) is more preferably 0.5 or less, even more preferably 0.3 or less, and particularly preferably 0.2 or less. Here, in the above relationship (1), Si (111) is the diffraction intensity of the Si (111) plane (planar spacing d=0.3135 nm), and Mg2Si (111) is the diffraction intensity of the Mg2Si (111) plane (planar spacing d=0.3668 nm).
[0031] In addition, the method for measuring Si(111) and Mg2Si(111) by the X-ray diffraction can be calculated by mechanically cutting a part of the plating film, powdering it, and performing X-ray diffraction (powder X-ray diffraction measurement method). Regarding the measurement of diffraction intensity, the diffraction peak intensity of Si corresponding to the interplanar spacing d=0.3135 nm and the diffraction peak intensity of Mg2Si corresponding to the interplanar spacing d=0.3668 nm are measured, and the ratio of these is calculated to obtain Si(111) / Mg2Si(111). The amount of the plating film required for carrying out the powder X-ray diffraction measurement (amount of the plating film to be scraped off) is 0.1 g or more, preferably 0.3 g or more, from the viewpoint of accurately measuring Si (111) and Mg2Si (111). In addition, when the plating film is scraped off, steel sheet components other than the plating film may be contained in the powder, but these intermetallic compound phases are contained only in the plating film and do not affect the above-mentioned peak intensity. Furthermore, the plating film is powdered and X-ray diffraction is carried out because, when X-ray diffraction is carried out on the plating film formed on the plated steel sheet, it is affected by the plane orientation of the plating film solidification structure, making it difficult to calculate the correct phase ratio.
[0032] Furthermore, in the hot-dip Al-Zn-Si-Mg plated steel sheet of the present invention, from the viewpoint of enabling more stable improvement in corrosion resistance, it is preferable that the diffraction intensity of Si in the plated film, as determined by an X-ray diffraction method, satisfies the following relationship (2): Si(111)=0 (2) Si (111): Diffraction intensity of the Si (111) plane (plane spacing d = 0.3135 nm) In general, it is known that in the dissolution reaction of an Al alloy in an aqueous solution, the presence of a Si phase as a cathode site promotes the dissolution of the surrounding α-Al phase. Therefore, reducing the amount of Si phase is also effective in terms of suppressing the dissolution of the α-Al phase. Among these, a coating in which no Si phase exists, as shown in relationship (2) (the diffraction peak intensity of the Si(111) is set to zero) is the most excellent in terms of stabilizing corrosion resistance. The method for measuring the diffraction peak intensity of the Si (111) plane by X-ray diffraction is as described above.
[0033] Here, the method for satisfying the above-mentioned relationship (1) and relationship (2) is not particularly limited. For example, in order to satisfy the relationship (1) and relationship (2), the abundance ratio of Mg2Si and Si (diffraction intensity of Mg2Si (111) and Si (111)) can be controlled by adjusting the balance of the Si content, Mg content, and Al content in the plating film. Note that the balance of the Si content, Mg content, and Al content in the plating film does not necessarily satisfy the relationship (1) and relationship (2) by setting the content ratio of Si, Mg content, and Al to a constant content ratio, and it is necessary to change the content ratio of Mg and Al depending on the Si content (mass%), for example. In addition to adjusting the balance of the Si content, the Mg content, and the Al content in the plating film, the diffraction intensities of MgSi(111) and Si(111) can be controlled so as to satisfy the relationship (1) or (2) by adjusting the conditions for forming the plating film (e.g., the cooling conditions after plating).
[0034] The coating weight of the plating film is set to 45 to 120 g / m per side from the viewpoint of satisfying various characteristics. 2 It is preferable that the coating weight of the plating film is 45 g / m 2 In the above cases, sufficient corrosion resistance is obtained for applications requiring long-term corrosion resistance, such as building materials, and the coating weight of the plating film is 120 g / m 2 This is because, in the following cases, it is possible to realize excellent corrosion resistance while suppressing the occurrence of plating cracks during processing. From the same viewpoint, the coating weight of the plating film is 45 to 100 g / m 2 It is more preferable that: The coating weight of the plating film can be derived, for example, by a method in which a specific area of the plating film is dissolved and peeled off with a mixed solution of hydrochloric acid and hexamethylenetetramine as specified in JIS H 0401: 2013, and the coating weight is calculated from the difference in the weight of the steel sheet before and after peeling. To determine the coating weight per side using this method, the plating surface of the non-target side is sealed with tape so as not to be exposed, and then the above-mentioned dissolution is carried out.
[0035] Furthermore, the base steel sheet constituting the hot-dip Al-Zn-Si-Mg-plated steel sheet of the present invention is not particularly limited, and a cold-rolled steel sheet, a hot-rolled steel sheet, or the like can be used as appropriate depending on the required performance and specifications. The method for obtaining the base steel sheet is not particularly limited. For example, in the case of the hot-rolled steel sheet, one that has been subjected to a hot rolling process and a pickling process can be used, and in the case of the cold-rolled steel sheet, it can be manufactured by further adding a cold rolling process. Furthermore, in order to obtain the properties of the steel sheet, it is also possible to pass through a recrystallization annealing process or the like before the hot-dip plating process.
[0036] The method for producing the hot-dip Al-Zn-Si-Mg-plated steel sheet of the present invention is not particularly limited. For example, the steel sheet can be produced by cleaning, heating, and immersing the base steel sheet in a plating bath in a continuous hot-dip plating facility. In the heating process of the steel sheet, recrystallization annealing or the like is performed to control the structure of the base steel sheet itself, and heating in a reducing atmosphere such as a nitrogen-hydrogen atmosphere is effective in preventing oxidation of the steel sheet and reducing a small amount of oxide film present on the surface.
[0037] As for the plating bath used in producing the hot-dip Al-Zn-Si-Mg plated steel sheet of the present invention, as described above, the composition of the plating film as a whole is substantially the same as the composition of the plating bath, and therefore a plating bath having a composition containing 45 to 65 mass% Al, 1.0 to 3.0 mass% Si, 1.0 to 10.0 mass% Mg, 0.1 to 0.5 mass% Mn, with the balance being Zn, Fe, and unavoidable impurities can be used.
[0038] Furthermore, the bath temperature of the plating bath is not particularly limited, but is preferably in the range of (melting point + 20°C) to 650°C. The reason why the lower limit of the bath temperature is set to the melting point + 20°C is that the bath temperature needs to be at or above the solidification point in order to perform hot-dip plating, and setting the temperature at the melting point + 20°C prevents solidification due to a local drop in the bath temperature of the plating bath. On the other hand, the reason why the upper limit of the bath temperature is set to 650°C is that if the bath temperature exceeds 650°C, it becomes difficult to rapidly cool the plating film, and there is a risk that the interfacial alloy layer formed between the plating film and the steel sheet will become thick.
[0039] In addition, the temperature of the base steel sheet immersed in the coating bath (immersion sheet temperature) is not particularly limited, but from the viewpoint of ensuring the coating characteristics in continuous hot-dip coating operations and preventing changes in the bath temperature, it is preferable to control it to within ±20°C of the coating bath temperature. Furthermore, the immersion time of the base steel sheet in the plating bath is 0.5 seconds or more. This is because if it is less than 0.5 seconds, there is a risk that a sufficient plating film may not be formed on the surface of the base steel sheet. There is no particular upper limit to the immersion time, but since a longer immersion time may cause a thicker interface alloy layer to form between the plating film and the steel sheet, it is preferable to set the immersion time to 8 seconds or less.
[0040] In addition, in the case of the hot-dip Al-Zn-Si-Mg plated steel sheet, a coating film can be formed directly or via an intermediate layer on the plated film, depending on the required performance. The method for forming the coating film is not particularly limited and can be appropriately selected depending on the required performance. For example, the coating film can be formed by a method such as roll coater coating, curtain flow coating, spray coating, etc. After coating the coating material containing an organic resin, the coating film can be formed by heating and drying the coating film by means of hot air drying, infrared heating, induction heating, etc. The intermediate layer is not particularly limited as long as it is a layer formed between the plating film of the hot-dip plated steel sheet and the coating film.
[0041] <Surface-treated steel sheet> The surface-treated steel sheet of the present invention comprises a plating film on the surface of the steel sheet, and a chemical conversion film formed on the plating film. The composition of the plating film is the same as that of the plating film of the above-mentioned hot-dip Al-Zn-Si-Mg plated steel sheet of the present invention. Other configurations of the plating film are also the same as those of the plating film of the hot-dip Al-Zn-Si-Mg-plated steel sheet of the present invention described above.
[0042] In the surface-treated steel sheet of the present invention, a chemical conversion coating is formed on the coating. The chemical conversion coating may be formed on at least one side of the surface-treated steel sheet, but may also be formed on both sides of the surface-treated steel sheet depending on the application and required performance.
[0043] In the surface-treated steel sheet of the present invention, the chemical conversion coating is characterized by containing at least one resin selected from epoxy resins, urethane resins, acrylic resins, acrylic silicone resins, alkyd resins, polyester resins, polyalkylene resins, amino resins, and fluororesins, and at least one metal compound selected from P compounds, Si compounds, Co compounds, Ni compounds, Zn compounds, Al compounds, Mg compounds, V compounds, Mo compounds, Zr compounds, Ti compounds, and Ca compounds. By forming the above-mentioned chemical conversion film on the plating film, it is possible to increase the affinity with the plating film, and to form the chemical conversion film uniformly on the plating film, and it is also possible to increase the rust prevention effect and barrier effect of the chemical conversion film, thereby making it possible to realize stable corrosion resistance and white rust resistance of the surface-treated steel sheet of the present invention.
[0044] Here, from the viewpoint of improving corrosion resistance, at least one resin selected from epoxy resin, urethane resin, acrylic resin, acrylic silicone resin, alkyd resin, polyester resin, polyalkylene resin, amino resin, and fluororesin is used as the resin constituting the conversion coating. From the same viewpoint, it is preferable that the resin contains at least one of urethane resin and acrylic resin. The resin constituting the conversion coating also includes an addition polymer of the above-mentioned resin.
[0045] As the epoxy resin, for example, glycidyl etherified epoxy resins such as bisphenol A type, bisphenol F type, and novolac type epoxy resins, glycidyl etherified bisphenol A type epoxy resins with added propylene oxide, ethylene oxide, or polyalkylene glycol, aliphatic epoxy resins, alicyclic epoxy resins, polyether-based epoxy resins, and the like can be used.
[0046] As the urethane resin, for example, an oil-modified polyurethane resin, an alkyd-based polyurethane resin, a polyester-based polyurethane resin, a polyether-based polyurethane resin, a polycarbonate-based polyurethane resin, or the like can be used.
[0047] Examples of the acrylic resin include polyacrylic acid and copolymers thereof, polyacrylic acid esters and copolymers thereof, polymethacrylic acid and copolymers thereof, polymethacrylic acid esters and copolymers thereof, urethane-acrylic acid copolymers (or urethane-modified acrylic resins), styrene-acrylic acid copolymers, and the like. Furthermore, these resins modified with other alkyd resins, epoxy resins, phenolic resins, and the like can be used.
[0048] The acrylic silicone resin may be, for example, a resin having a hydrolyzable alkoxysilyl group at the side chain or end of an acrylic copolymer as a base material, to which a curing agent is added, etc. In addition, when using an acrylic silicone resin, excellent weather resistance can be expected in addition to corrosion resistance.
[0049] Examples of the alkyd resin include oil-modified alkyd resins, rosin-modified alkyd resins, phenol-modified alkyd resins, styrenated alkyd resins, silicon-modified alkyd resins, acrylic-modified alkyd resins, oil-free alkyd resins, and high molecular weight oil-free alkyd resins.
[0050] The polyester resin is a polycondensate synthesized by dehydration condensation of a polycarboxylic acid and a polyalcohol to form an ester bond, and examples of the polycarboxylic acid include terephthalic acid and 2,6-naphthalenedicarboxylic acid, and examples of the polyalcohol include ethylene glycol, 1,3-propanediol, 1,4-butanediol, and 1,4-cyclohexanedimethanol. Specific examples of the polyester include polyethylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, and polybutylene naphthalate. These polyester resins modified with acrylic may also be used.
[0051] Examples of the polyalkylene resin include ethylene-based copolymers such as ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, and carboxyl-modified polyolefin resins, ethylene-unsaturated carboxylic acid copolymers, and ethylene-based ionomers. Furthermore, these resins modified with other alkyd resins, epoxy resins, phenolic resins, and the like can be used.
[0052] The amino resin is a thermosetting resin produced by the reaction of an amine or amide compound with an aldehyde, and examples of the resin include melamine resin, guanamine resin, and thiourea resin, with melamine resin being preferred from the viewpoints of corrosion resistance, weather resistance, adhesion, etc. The melamine resin is not particularly limited, but examples thereof include butylated melamine resin, methylated melamine resin, and aqueous melamine resin.
[0053] Examples of the fluororesin include fluoroolefin polymers and copolymers of fluoroolefin with alkyl vinyl ether, cycloalkyl vinyl ether, carboxylic acid-modified vinyl ester, hydroxyalkyl allyl ether, tetrafluoropropyl vinyl ether, etc. When these fluororesins are used, not only corrosion resistance but also excellent weather resistance and excellent hydrophobicity can be expected.
[0054] Furthermore, in order to improve corrosion resistance and workability, it is particularly preferable to use a curing agent for the resin constituting the chemical conversion coating. As the curing agent, amino resins such as urea resins (butylated urea resins, etc.), melamine resins (butylated melamine resins, butyl etherified melamine resins, etc.), butylated urea-melamine resins, and benzoguanamine resins, blocked isocyanates, oxazoline compounds, and phenolic resins can be appropriately used.
[0055] The metal compound constituting the chemical conversion coating is at least one selected from the group consisting of P compounds, Si compounds, Co compounds, Ni compounds, Zn compounds, Al compounds, Mg compounds, V compounds, Mo compounds, Zr compounds, Ti compounds, and Ca compounds. From the same viewpoint, it is preferable that the metal compound contains at least one of P compounds, Si compounds, and V compounds.
[0056] The P compound contained in the chemical conversion coating can improve corrosion resistance and sweat resistance. The P compound is a compound containing P, and can contain, for example, one or more selected from inorganic phosphoric acid, organic phosphoric acid, and salts thereof.
[0057] The inorganic phosphoric acid, organic phosphoric acid, and salts thereof are not particularly limited and any compound can be used. For example, the inorganic phosphoric acid is preferably one or more selected from phosphoric acid, primary phosphate, secondary phosphate, tertiary phosphate, pyrophosphoric acid, pyrophosphate, tripolyphosphoric acid, tripolyphosphate, phosphorous acid, phosphite, hypophosphorous acid, and hypophosphite. The organic phosphoric acid is preferably phosphonic acid (phosphonic acid compound). The phosphonic acid is preferably one or more selected from nitrilotrismethylenephosphonic acid, phosphonobutanetricarboxylic acid, methyldiphosphonic acid, methylenephosphonic acid, and ethylidenediphosphonic acid. When the P compound is a salt, the salt is preferably a salt of an element of Groups 1 to 13 in the periodic table, more preferably a metal salt, and is preferably one or more selected from alkali metal salts and alkaline earth metal salts.
[0058] When the chemical conversion treatment solution containing the above-mentioned P compound is applied to a plated steel sheet, the surface of the plated film is etched by the action of the P compound, and a concentrated layer containing Al, Zn, Si, and Mg, which are the constituent elements of the plated film, is formed on the plated film side of the chemical conversion film. The formation of the concentrated layer strengthens the bond between the chemical conversion film and the plated film surface, improving the adhesion of the chemical conversion film. The concentration of the P compound in the chemical conversion treatment solution is not particularly limited, but can be 0.25% by mass to 5% by mass. If the concentration of the P compound is less than 0.25% by mass, the etching effect is insufficient, the adhesion to the plating interface is reduced, and not only the corrosion resistance of the flat surface is reduced, but also the corrosion resistance and sweat resistance of defective parts, cut end faces, and damaged parts of the plating and film caused by processing may be reduced. From the same viewpoint, the concentration of the P compound is preferably 0.35% by mass or more, more preferably 0.50% by mass or more. On the other hand, if the concentration of the P compound exceeds 5% by mass, not only the life of the chemical conversion treatment solution is shortened, but also the appearance of the film when formed is likely to be non-uniform, and the amount of P eluted from the chemical conversion film increases, which may reduce the resistance to blackening. From the same viewpoint, the concentration of the P compound is preferably 3.5% by mass or less, more preferably 2.5% by mass or less. Regarding the content of the P compound in the chemical conversion coating, for example, a chemical conversion treatment solution containing a P compound at a concentration of 0.25% by mass to 5% by mass is applied and dried, so that the amount of P attached in the chemical conversion coating after drying is 5 to 100 mg / m 2 It can be said that:
[0059] The Si compound is a component that becomes a framework for forming a chemical conversion coating together with the resin, and can enhance affinity with the plating coating to form a uniform chemical conversion coating. The Si compound is a compound containing Si, and preferably contains one or more selected from, for example, silica, trialkoxysilane, tetraalkoxysilane, and a silane coupling agent.
[0060] The silica is not particularly limited and any silica can be used. For example, at least one of wet silica and dry silica can be used. For example, Snowtex O, C, N, S, 20, OS, OXS, NS, etc. manufactured by Nissan Chemical Industries, Ltd. can be suitably used as colloidal silica, which is a type of wet silica. For example, AEROSIL 50, 130, 200, 300, 380, etc. manufactured by Nippon Aerosil Co., Ltd. can be suitably used as the dry silica.
[0061] The trialkoxysilane is not particularly limited and any trialkoxysilane can be used. For example, it is preferable to use a trialkoxysilane represented by the general formula: R1Si(OR2)3 (wherein R1 is hydrogen or an alkyl group having 1 to 5 carbon atoms, and R2 is the same or different alkyl group having 1 to 5 carbon atoms). Examples of such trialkoxysilane include trimethoxysilane, triethoxysilane, and methyltriethoxysilane.
[0062] The tetraalkoxysilane is not particularly limited and any tetraalkoxysilane can be used. For example, it is preferable to use a tetraalkoxysilane represented by the general formula: Si(OR)4 (wherein R is the same or different alkyl group having 1 to 5 carbon atoms). Examples of such tetraalkoxysilane include tetramethoxysilane, tetraethoxysilane, and tetrapropoxysilane.
[0063] The silane coupling agent is not particularly limited and any one can be used. For example, γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl methyl diethoxysilane, γ-glycidoxypropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl methyl diethoxysilane, γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl triethoxysilane, γ-mercaptopropyl methyl dimethoxysilane, γ-mercaptopropyl trimethoxysilane, vinyl triethoxysilane, γ-isocyanate propyl triethoxysilane, etc. can be mentioned.
[0064] By incorporating the Si compound in the chemical conversion film, the Si compound undergoes dehydration condensation to form an amorphous chemical conversion film having siloxane bonds that have a high barrier effect of shielding corrosion factors. In addition, by bonding with the above-mentioned resin, a chemical conversion film with higher barrier properties is formed. Furthermore, in a corrosive environment, dense and stable corrosion products are formed in defective parts or damaged parts of the plating or film caused by processing, etc., and the combined effect with the plating film also has the effect of suppressing corrosion of the base steel sheet. From the viewpoint of a high effect of forming a stable corrosion product, it is preferable to use at least one of colloidal silica and dry silica as the Si compound.
[0065] The concentration of the Si compound in the chemical conversion treatment liquid for forming the chemical conversion coating is 0.2% by mass to 9.5% by mass. If the concentration of the Si compound in the chemical conversion treatment liquid is 0.2% by mass or more, a barrier effect due to siloxane bonds can be obtained, and as a result, in addition to the corrosion resistance of flat surfaces, the corrosion resistance of defective parts, cut parts, and parts damaged due to processing, etc., and sweat resistance are improved. Furthermore, if the concentration of the Si compound is 9.5% by mass or less, the life of the chemical conversion treatment liquid can be extended. By applying and drying a chemical conversion treatment liquid with a Si compound concentration of 0.2% by mass to 9.5% by mass, the Si adhesion amount in the chemical conversion coating after drying can be 2 to 95 mg / m 2 It can be said that:
[0066] The Co compound and the Ni compound contained in the chemical conversion coating can improve the blackening resistance. This is believed to be because Co and Ni have the effect of delaying the elution of water-soluble components from the coating in a corrosive environment. In addition, the Co and Ni are elements that are less likely to be oxidized than Al, Zn, Si, Mg, and the like. Therefore, by concentrating (forming a concentrated layer) at least one of the Co compound and the Ni compound at the interface between the chemical conversion coating and the plating coating, the concentrated layer becomes a barrier against corrosion, and as a result, the blackening resistance can be improved.
[0067] By using a chemical conversion treatment solution containing the Co compound, Co can be contained in the chemical conversion coating and incorporated into the concentrated layer. As the Co compound, a cobalt salt is preferably used. As the cobalt salt, one or more selected from cobalt sulfate, cobalt carbonate, and cobalt chloride are more preferably used. In addition, by using a chemical conversion treatment solution containing the Ni compound, Ni can be contained in the chemical conversion coating and incorporated into the concentrated layer. As the Ni compound, a nickel salt is preferably used. As the nickel salt, it is more preferable to use one or more selected from nickel sulfate, nickel carbonate, and nickel chloride.
[0068] The concentration of the Co compound and / or Ni compound in the chemical conversion treatment liquid is not particularly limited, but can be 0.25 mass% to 5 mass% in total. If the concentration of the Co compound and / or Ni compound is less than 0.25 mass%, the interface thickened layer becomes nonuniform, and not only the corrosion resistance of the flat portion decreases, but also the corrosion resistance of the plating or film damaged portion caused by defects, cut end faces, processing, etc. may decrease. From the same viewpoint, it is preferably 0.5 mass% or more, more preferably 0.75 mass% or more. On the other hand, if the concentration of the Co compound and / or Ni compound exceeds 5 mass%, the appearance of the formed film is likely to become nonuniform, and the corrosion resistance may decrease. From the same viewpoint, it is preferably 4.0 mass% or less, more preferably 3.0 mass% or less. By applying and drying the chemical conversion treatment liquid having a total concentration of the Co compound and / or Ni compound of 0.25 mass% to 5 mass%, the total adhesion amount of Co and Ni in the chemical conversion film after drying is 5 to 100 mg / m 2 It can be said that:
[0069] The Al compound, the Zn compound, and the Mg compound are contained in the chemical conversion treatment solution, so that a concentrated layer containing at least one of Al, Zn, and Mg can be formed on the plating film side of the chemical conversion film. The formed concentrated layer can improve corrosion resistance. The Al compound, the Zn compound, and the Mg compound are not particularly limited as long as they are compounds containing Al, Zn, and Mg, respectively, but are preferably inorganic compounds, and are preferably salts, chlorides, oxides, or hydroxides.
[0070] The Al compound may be, for example, one or more selected from aluminum sulfate, aluminum carbonate, aluminum chloride, aluminum oxide, and aluminum hydroxide. The Zn compound may be, for example, one or more selected from zinc sulfate, zinc carbonate, zinc chloride, zinc oxide, and zinc hydroxide. The Mg compound may be, for example, one or more selected from magnesium sulfate, magnesium carbonate, magnesium chloride, magnesium oxide, and magnesium hydroxide.
[0071] The total concentration of the Al compound, Zn compound and / or Mg compound in the chemical conversion treatment solution for forming the chemical conversion coating is preferably 0.25% by mass to 5% by mass. If the total concentration is 0.25% by mass or more, the concentrated layer can be formed more effectively, and as a result, the corrosion resistance can be further improved. On the other hand, if the total concentration is 5% by mass or less, the appearance of the chemical conversion coating becomes more uniform, and the corrosion resistance of flat parts, defective parts, and damaged parts of the plating or coating caused by processing, etc. is further improved.
[0072] The V compound contained in the chemical conversion coating allows the V to be appropriately dissolved in a corrosive environment and to bond with zinc ions and other plating components that also dissolve in a corrosive environment to form a dense protective coating. The formed protective coating can further increase corrosion resistance not only to the flat surface of the steel sheet, but also to defects, damaged areas of the plating coating caused by processing, corrosion that progresses from the cut end surface to the flat surface, and the like.
[0073] The V compound is a compound containing V, and examples thereof include one or more selected from sodium metavanadate, vanadyl sulfate, and vanadium acetylacetonate.
[0074] The V compound in the chemical conversion treatment solution for forming the chemical conversion coating is preferably 0.05% by mass to 4% by mass. If the concentration of the V compound is 0.05% by mass or more, it is easy to dissolve in a corrosive environment to form a protective coating, and the corrosion resistance of defective parts, cut end faces, and damaged parts of the plating coating caused by processing is improved. On the other hand, if the concentration of the V compound exceeds 4% by mass, the appearance of the formed chemical conversion coating is likely to be non-uniform, and the resistance to blackening is also reduced.
[0075] The Mo compound, when contained in the chemical conversion coating, can enhance the blackening resistance of the surface-treated steel sheet. The Mo compound is a compound containing Mo, and can be obtained by adding one or both of molybdic acid and a molybdate to the chemical conversion treatment solution. The molybdate may be, for example, one or more selected from sodium molybdate, potassium molybdate, magnesium molybdate, and zinc molybdate.
[0076] The concentration of the Mo compound in the chemical conversion treatment solution for forming the chemical conversion coating is preferably 0.01% by mass to 3% by mass. If the concentration of the Mo compound is 0.01% by mass or more, the generation of oxygen-deficient zinc oxide is further suppressed, and blackening resistance can be further improved. On the other hand, if the concentration of the Mo compound is 3% by mass or less, the life of the chemical conversion treatment solution is further extended and corrosion resistance can be further improved.
[0077] The Zr compound and the Ti compound contained in the chemical conversion coating can prevent the chemical conversion coating from becoming porous and can densify the coating, which makes it difficult for corrosive factors to permeate the chemical conversion coating and improves corrosion resistance.
[0078] The Zr compound is a compound containing Zr, and for example, one or more selected from zirconyl acetate, zirconyl sulfate, potassium zirconyl carbonate, sodium zirconyl carbonate, and ammonium zirconyl carbonate can be used. Among these, organic titanium chelate compounds are preferred because they densify the film when the chemical conversion treatment liquid is dried to form the film, thereby obtaining better corrosion resistance.
[0079] The Ti compound is a compound containing Ti, and for example, one or more selected from titanium sulfate, titanium chloride, titanium hydroxide, titanium acetylacetonate, titanium octylene glycolate, and titanium ethylacetoacetate can be used.
[0080] The concentration of the Zr compound and / or Ti compound in the chemical conversion treatment solution for forming the chemical conversion film is preferably 0.2% by mass to 20% by mass in total. If the total concentration of the Zr compound and / or Ti compound is 0.2% by mass or more, the effect of inhibiting the permeation of corrosion factors is enhanced, and the corrosion resistance of not only the flat surface corrosion resistance but also the corrosion resistance of defective parts, cut end faces, and parts of the plating film damaged by processing can be further improved. On the other hand, if the total concentration of the Zr compound and / or Ti compound is 20% by mass or less, the life of the chemical conversion treatment solution can be further extended.
[0081] The Ca compound contained in the chemical conversion coating can exert an effect of reducing the corrosion rate.
[0082] The Ca compound is a compound containing Ca, and examples of the Ca compound include Ca oxide, Ca nitrate, Ca sulfate, and intermetallic compounds containing Ca. More specifically, examples of the Ca compound include CaO, CaCO3, Ca(OH)2, Ca(NO3)2·4H2O, and CaSO4·2H2O. The content of the Ca compound in the chemical conversion coating is not particularly limited.
[0083] The chemical conversion coating may contain various known components commonly used in the coating field, as necessary, such as various surface conditioners, such as leveling agents and antifoaming agents, various additives, such as dispersants, anti-settling agents, ultraviolet absorbers, light stabilizers, silane coupling agents and titanate coupling agents, various pigments, such as color pigments, extender pigments and luster materials, curing catalysts, organic solvents and lubricants.
[0084] In the surface-treated steel sheet of the present invention, the chemical conversion coating preferably does not contain harmful components such as hexavalent chromium, trivalent chromium, fluorine, etc. This is because the chemical conversion treatment solution for forming the chemical conversion coating does not contain these harmful components, resulting in high safety and low environmental impact.
[0085] The coating weight of the chemical conversion coating is not particularly limited. For example, from the viewpoint of preventing peeling of the chemical conversion coating while more reliably securing corrosion resistance, the coating weight of the chemical conversion coating is set to 0.1 to 3.0 g / m 2 It is preferable to set the thickness to 0.5 to 2.5 g / m 2 It is more preferable that the coating weight of the chemical conversion coating is 0.1 g / m 2 By setting the coating weight at 3.0 g / m or more, corrosion resistance can be more reliably ensured, and the coating weight of the chemical conversion film is 3.0 g / m or more. 2 By setting the temperature below 100° C., cracking and peeling of the chemical conversion coating can be prevented. The coating weight of the chemical conversion coating may be determined by a method appropriately selected from existing techniques, such as a method of subjecting the coating to fluorescent X-ray analysis to measure the amount of an element present in the coating whose content is known in advance.
[0086] The method for forming the chemical conversion coating is not particularly limited, and can be appropriately selected according to the required performance, manufacturing equipment, etc. For example, the chemical conversion coating can be formed by continuously applying a chemical conversion treatment solution onto the plating film using a roll coater or the like, and then drying at a peak metal temperature (PMT) of about 60 to 200°C using hot air or induction heating. In addition to the roll coater, known methods such as airless spray, electrostatic spray, and curtain flow coater can be appropriately used to apply the chemical conversion treatment solution. Furthermore, the chemical conversion coating may be either a single-layer film or a multi-layer film as long as it contains the resin and the metal compound, and is not particularly limited.
[0087] The surface-treated steel sheet of the present invention has a height difference of 10 μm or less per mm length in a range excluding 50 mm from both ends of the steel sheet surface (chemical conversion coating surface), similar to the surface of the hot-dip Al-Zn-Si-Mg-plated steel sheet of the present invention described above. When the height difference of the surface of the chemical conversion coating is 10 μm or less, there are no wrinkle-like defects and an excellent surface appearance can be obtained. As described above, the wrinkle defects are defects in which the surface of the chemical conversion coating is wrinkled and uneven due to Mg-based oxides, and appear as white streaks on the surface of the chemical conversion coating. Therefore, suppressing the wrinkle defects means that the streaks are not visible. Therefore, by suppressing the height difference within a 1 mm long range of the steel sheet surface, i.e., the chemical conversion coating surface, to within 10 μm, the streaks are not visible, and an excellent surface appearance can be obtained. From the same viewpoint, it is preferable that the height difference within a 1 mm long range of the steel sheet surface is within 5 μm. The steel sheet surface means the outermost surface of the steel sheet, and in the case of a surface-treated steel sheet, means the surface of the chemical conversion coating. As in the case of the plating coating surface described above, the height difference within a 1 mm length range of the chemical conversion coating surface can be obtained by measuring the height differences within a 1 mm length range at any 100 points on the surface-treated steel sheet using a laser microscope and calculating the average of the measured values.
[0088] The reason for controlling the height difference on the surface of the steel sheet in the range excluding 50 mm from both ends of the steel sheet is that, in general, it is difficult to control the coating weight at both ends of a hot-dip galvanized steel sheet compared to the center of the steel sheet, and the cooling rate is also different, so wrinkle-like defects are likely to occur. In addition, such both ends of the steel sheet are often trimmed before use, so there is almost no problem with the surface appearance.
[0089] As for a method for controlling the height difference of the coating surface to 10 μm or less per 1 mm of length of the steel sheet surface, it is important to suppress the height difference of the plating coating surface described above, and the height difference of the coating surface can be suppressed by adjusting the Mg / Mn content ratio in the plating coating or by performing other surface treatments for suppressing the height difference.
[0090] In addition, in the surface-treated steel sheet of the present invention, a paint film can be formed on the chemical conversion film, if necessary.
[0091] The method for producing a surface-treated steel sheet of the present invention is a method for producing a surface-treated steel sheet comprising a plating film and a chemical conversion film formed on the plating film. In the manufacturing method of the present invention, the chemical conversion coating contains at least one resin selected from the group consisting of epoxy resins, urethane resins, acrylic resins, acrylic silicone resins, alkyd resins, polyester resins, polyalkylene resins, amino resins, and fluororesins, and at least one metal compound selected from the group consisting of P compounds, Si compounds, Co compounds, Ni compounds, Zn compounds, Al compounds, Mg compounds, V compounds, Mo compounds, Zr compounds, Ti compounds, and Ca compounds, The formation of the plating film includes a hot-dip galvanizing process in which the base steel sheet is immersed in a plating bath having a composition containing 45 to 65 mass% Al, 1.0 to 4.0 mass% Si, and 1.0 to 10.0 mass% Mg, with the balance being Zn and unavoidable impurities.
[0092] The conditions for the hot-dip galvanizing process are the same as those explained in the description of the hot-dip Al-Zn-Si-Mg-plated steel sheet of the present invention.
[0093] <Painted steel plate> The coated steel sheet of the present invention is a coated steel sheet in which a coating film is formed on a plating film directly or via a chemical conversion film. The composition of the plating film is the same as that of the plating film of the above-mentioned hot-dip Al-Zn-Si-Mg plated steel sheet of the present invention. Other configurations of the plating film are also the same as those of the plating film of the hot-dip Al-Zn-Si-Mg-plated steel sheet of the present invention described above.
[0094] In the coated steel sheet of the present invention, a chemical conversion film can be formed on the plating film. The chemical conversion coating may be formed on at least one side of the coated steel sheet, and may also be formed on both sides of the coated steel sheet depending on the application and required performance.
[0095] Chemical coating The coated steel sheet of the present invention is characterized in that the chemical conversion coating contains a resin component that contains 30 to 50 mass% in total of (a): an anionic polyurethane resin having an ester bond and (b): an epoxy resin having a bisphenol skeleton, the content ratio of (a):(b) being within a range of 3:97 to 60:40 in terms of mass ratio, and inorganic compounds that include 2 to 10 mass% of a vanadium compound, 40 to 60 mass% of a zirconium compound, and 0.5 to 5 mass% of a fluorine compound. By forming the above-mentioned chemical conversion film on the plating film, the strength and adhesion of the chemical conversion film can be increased, and the corrosion resistance can also be improved.
[0096] Here, the resin components constituting the chemical conversion coating include (a): an anionic polyurethane resin having an ester bond and (b): an epoxy resin having a bisphenol skeleton.
[0097] The (a) anionic polyurethane resin having an ester bond may be a resin obtained by copolymerizing a reaction product of a polyester polyol with a diisocyanate or polyisocyanate having two or more isocyanate groups with a dimethylol alkyl acid. A chemical conversion treatment liquid can be obtained by dispersing the reaction product in a liquid such as water by a known method.
[0098] Examples of the polyester polyol include polyesters obtained by a dehydration condensation reaction between a glycol component and an acid component such as an ester-forming derivative of a hydroxyl carboxylic acid, polyesters obtained by a ring-opening polymerization reaction of a cyclic ester compound such as ε-caprolactone, and copolymer polyesters thereof. Examples of the polyisocyanate include aromatic polyisocyanates, aliphatic polyisocyanates, and alicyclic polyisocyanates. Examples of the aromatic polyisocyanate include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, m-xylylene diisocyanate, diphenylmethane diisocyanate, 2,4-diphenylmethane diisocyanate, 2,2-diphenylmethane diisocyanate, triphenylmethane triisocyanate, polymethylene polyphenyl polyisocyanate, naphthalene diisocyanate, and derivatives thereof (e.g., prepolymers obtained by reaction with polyols, modified polyisocyanates such as carbodiimide compounds of diphenylmethane diisocyanate, etc.).
[0099] When the polyester polyol is reacted with the diisocyanate or polyisocyanate to synthesize urethane, the anionic polyurethane resin having the ester bond (a) can be obtained by, for example, copolymerizing a dimethylol alkyl acid and self-emulsifying it to be water-soluble (water-dispersed). In this case, examples of the dimethylol alkyl acid include dimethylol alkyl acids having 2 to 6 carbon atoms, more specifically, dimethylol ethanoic acid, dimethylol propanoic acid, dimethylol butanoic acid, dimethylol heptanoic acid, and dimethylol hexanoic acid.
[0100] In addition, the epoxy resin having a bisphenol skeleton (b) may be a known epoxy resin. Examples include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD type epoxy resin, and bisphenol S type epoxy resin. These epoxy resins can be obtained by reacting a bisphenol compound such as bisphenol A, bisphenol F, bisphenol AD, or bisphenol S with epichlorohydrin in the presence of an alkali catalyst. Among them, component [A] preferably contains a bisphenol A type epoxy resin or a bisphenol F type epoxy resin, and more preferably contains a bisphenol A type epoxy resin. The epoxy resin having a bisphenol skeleton (b) can be dispersed in a liquid such as water by a known method to obtain a chemical conversion treatment liquid.
[0101] The resin component acts as a binder for the chemical conversion coating, and the (a) anionic polyurethane resin having ester bonds that constitutes the binder is flexible and therefore has the effect of making the chemical conversion coating less likely to be destroyed (peeled off) when processed, and the (b) epoxy resin having a bisphenol skeleton has the effect of improving adhesion to the underlying zinc-based plated steel sheet and the upper primer coating film. The resin components are contained in the chemical conversion coating in a total amount of 30 to 50% by mass. If the content of the resin components is less than 30% by mass, the binder effect of the chemical conversion coating is reduced, and if it exceeds 50% by mass, the functions of the inorganic components described below, such as the inhibitor action, are reduced. From the same viewpoint, the content of the resin components in the chemical conversion coating is preferably 35 to 45% by mass.
[0102] Furthermore, the resin component must have a content ratio ((a):(b)) of the (a) anionic polyurethane resin having an ester bond and the (b) epoxy resin having a bisphenol skeleton in the range of 3:97 to 60:40 by mass. If the (a):(b) is outside the above range, the flexibility and adhesion of the chemical conversion coating film will decrease, and sufficient corrosion resistance will not be obtained. From the same viewpoint, the (a):(b) is preferably 10:90 to 55:45.
[0103] The resin component may contain resins (other resin components) other than the above-mentioned (a) anionic polyurethane resin having an ester bond and (b) epoxy resin having a bisphenol skeleton, depending on the required performance. The other resin components are not particularly limited, and may be, for example, at least one selected from acrylic resin, acrylic silicone resin, alkyd resin, polyester resin, polyalkylene resin, amino resin, and fluororesin, or a combination of two or more selected therefrom. When the resin component contains other resins, the total content of the (a) anionic polyurethane resin having an ester bond and the (b) epoxy resin having a bisphenol skeleton is preferably 50% by mass or more, and more preferably 75% by mass or more, in order to more reliably prevent a decrease in flexibility and obtain adhesion as a chemical treatment film.
[0104] The chemical conversion coating contains, as inorganic compounds, 2 to 10 mass % of a vanadium compound, 40 to 60 mass % of a zirconium compound, and 0.5 to 5 mass % of a fluorine compound. By including these compounds, the corrosion resistance of the chemical conversion coating can be improved.
[0105] The vanadium compound is added to a chemical conversion solution and acts as a rust inhibitor. When the vanadium compound is contained in the chemical conversion film, the vanadium compound is appropriately dissolved in a corrosive environment and combines with zinc ions and other plating components that also dissolve in a corrosive environment to form a dense protective film. The formed protective film can further increase corrosion resistance not only to the flat surface of the steel sheet, but also to defects, damaged areas of the plating film caused by processing, corrosion that progresses from the cut end surface to the flat surface, and the like. Examples of the vanadium compound include vanadium pentoxide, metavanadic acid, ammonium metavanadate, vanadium oxytrichloride, vanadium trioxide, vanadium dioxide, magnesium vanadate, vanadyl acetylacetonate, vanadium acetylacetonate, etc. Among these, it is particularly desirable to use a tetravalent vanadium compound or a tetravalent vanadium compound obtained by reduction or oxidation.
[0106] The content of the vanadium compound in the chemical conversion coating is 2 to 10 mass %. If the content of the vanadium compound in the chemical conversion coating is less than 2 mass %, the inhibitor effect is insufficient, resulting in a decrease in corrosion resistance, whereas if the content of the vanadium compound exceeds 10 mass %, the moisture resistance of the chemical conversion coating is decreased.
[0107] The zirconium compound is contained in the chemical conversion coating, and is expected to improve the strength and corrosion resistance of the chemical conversion coating through its reaction with the plating metal and its coexistence with a resin component. Furthermore, the zirconium compound itself contributes to the formation of a dense chemical conversion coating, and because of its excellent covering properties, a barrier effect can be expected. Examples of the zirconium compound include neutral salts of zirconium sulfate, zirconium carbonate, zirconium nitrate, zirconium lactate, zirconium acetate, zirconium chloride, and the like.
[0108] The content of the zirconium compound in the chemical conversion coating is 40 to 60 mass %. If the content of the zirconium compound in the chemical conversion coating is less than 40 mass %, the strength and corrosion resistance of the chemical conversion coating will decrease, whereas if the content of the zirconium compound exceeds 60 mass %, the chemical conversion coating will become embrittled, causing damage or peeling of the chemical conversion coating when subjected to severe processing.
[0109] The fluorine compound is contained in the chemical conversion coating and acts as an adhesive agent for the plating coating, thereby making it possible to improve the corrosion resistance of the chemical conversion coating. As the fluorine compound, for example, fluoride salts such as ammonium salts, sodium salts, potassium salts, or fluorine compounds such as ferrous fluoride, ferric fluoride, etc. Among these, it is preferable to use fluoride salts such as ammonium fluoride, sodium fluoride, and potassium fluoride.
[0110] Furthermore, the content of the fluorine compound in the chemical conversion coating is 0.5 to 5 mass %. If the content of the fluorine compound in the chemical conversion coating is less than 0.5 mass %, sufficient adhesion cannot be obtained at the processed portion, and if the content of the fluorine compound exceeds 5 mass %, the moisture resistance of the chemical conversion coating decreases.
[0111] The coating weight of the chemical conversion coating is not particularly limited. For example, from the viewpoint of improving the adhesion of the chemical conversion coating while more reliably ensuring corrosion resistance, the coating weight of the chemical conversion coating is set to 0.025 to 0.5 g / m. 2 It is preferable that the coating weight of the chemical conversion coating is 0.025 g / m 2 By setting the coating weight at 0.5 g / m or more, corrosion resistance can be more reliably ensured, and the coating weight of the chemical conversion film is 0.5 g / m or more. 2 By setting the following, peeling of the chemical conversion coating can be suppressed. The coating weight of the chemical conversion coating may be determined by a method appropriately selected from existing techniques, such as a method of subjecting the coating to fluorescent X-ray analysis to measure the amount of an element present in the coating whose content is known in advance.
[0112] The method for forming the chemical conversion coating is not particularly limited, and can be appropriately selected according to the required performance, manufacturing equipment, etc. For example, the chemical conversion coating can be formed by continuously applying a chemical conversion treatment solution onto the plating film using a roll coater or the like, and then drying at a peak metal temperature (PMT) of about 60 to 200°C using hot air or induction heating. In addition to the roll coater, known methods such as airless spray, electrostatic spray, and curtain flow coater can be appropriately used to apply the chemical conversion treatment solution. Furthermore, the chemical conversion coating may be either a single-layer film or a multi-layer film as long as it contains the resin and the metal compound, and is not particularly limited.
[0113] Coating As described above, the coated steel sheet of the present invention has a coating film formed directly or via a chemical conversion coating on a plating film, and the coating film has at least a primer coating film.
[0114] In the present invention, the primer coating film contains a polyester resin having a urethane bond, and an inorganic compound including a vanadium compound, a phosphate compound, and magnesium oxide. The primer coating film contains the polyester resin having a urethane bond and the inorganic compound, and therefore the adhesion of the coating film can be increased and the corrosion resistance can be improved.
[0115] The primer coating contains a polyester resin having a urethane bond as a main component. The polyester resin having a urethane bond is flexible and strong, so that the primer coating is less likely to crack when processed, and has a high affinity with a chemical conversion coating containing a urethane resin, so that the primer coating can particularly contribute to improving the corrosion resistance of processed parts. The term "main component" used herein means the component that is contained in the greatest amount among all the components in the primer coating film.
[0116] The polyester resin having a urethane bond may be a known resin such as a resin obtained by reacting a polyester polyol with a diisocyanate or polyisocyanate having two or more isocyanate groups. Also usable is a resin obtained by reacting the polyester polyol with the diisocyanate or polyisocyanate in an excess hydroxyl group state (urethane-modified polyester resin) with a blocked polyisocyanate.
[0117] The polyester polyol can be obtained by a known method utilizing a dehydration condensation reaction between a polyhydric alcohol component and a polybasic acid component. The polyhydric alcohol includes glycol and trihydric or higher polyhydric alcohol. Examples of the glycol include ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, neopentyl glycol, hexylene glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2-butyl-2-ethyl-1,3-propanediol, methylpropanediol, cyclohexanedimethanol, 3,3-diethyl-1,5-pentanediol, etc. Examples of the trihydric or higher polyhydric alcohol include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, dipentaerythritol, etc. These polyhydric alcohols can be used alone or in combination of two or more. The polybasic acid is usually a polyvalent carboxylic acid, but can be used in combination with a monovalent fatty acid if necessary. Examples of the polybasic acid include phthalic acid, tetrahydrophthalic acid, hexahydrophthalic acid, 4-methylhexahydrophthalic acid, bicyclo[2,2,1]heptane-2,3-dicarboxylic acid, trimellitic acid, adipic acid, sebacic acid, succinic acid, azelaic acid, fumaric acid, maleic acid, itaconic acid, pyromellitic acid, dimer acid, and the like, and their acid anhydrides, as well as 1,4-cyclohexanedicarboxylic acid, isophthalic acid, tetrahydroisophthalic acid, hexahydroisophthalic acid, hexahydroterephthalic acid, and the like. These polybasic acids can be used alone or in combination of two or more.
[0118] Examples of the polyisocyanate include aliphatic diisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and dimer acid diisocyanate, aromatic diisocyanates such as xylylene diisocyanate (XDI), metaxylylene diisocyanate, tolylene diisocyanate (TDI), and 4,4-diphenylmethane diisocyanate (MDI), and further cyclic aliphatic diisocyanates such as isophorone diisocyanate, hydrogenated XDI, hydrogenated TDI, and hydrogenated MDI, as well as adducts, biurets, and isocyanurates thereof. These polyisocyanates can be used alone or in combination of two or more.
[0119] In addition, the hydroxyl value of the polyester resin having a urethane bond is not particularly limited, but from the viewpoints of solvent resistance, processability, etc., it is preferably 5 to 120 mgKOH / g, more preferably 7 to 100 mgKOH / g, and even more preferably 10 to 80 mgKOH / g. Furthermore, the number average molecular weight of the polyester resin having a urethane bond is preferably from 500 to 15,000, more preferably from 700 to 12,000, and even more preferably from 800 to 10,000, from the viewpoints of solvent resistance, processability, and the like.
[0120] The content of the polyester resin having a urethane bond in the primer coating is preferably 40 to 88% by mass. If the content of the polyester resin having a urethane bond is less than 40% by mass, the binder function of the primer coating may be reduced, whereas if the content of the polyester resin having a urethane bond exceeds 88% by mass, the inorganic functions described below, such as the inhibitor action, may be reduced.
[0121] Vanadium compounds, which are one of the inorganic compounds, act as inhibitors. Examples of the vanadium compounds include vanadium pentoxide, metavanadic acid, ammonium metavanadate, vanadium oxytrichloride, vanadium trioxide, vanadium dioxide, magnesium vanadate, vanadyl acetylacetonate, vanadium acetylacetonate, etc. In particular, among these, it is desirable to use a tetravalent vanadium compound or a tetravalent vanadium compound obtained by reduction or oxidation. The vanadium compound added to the primer coating may be the same or different from the vanadium compound added to the chemical conversion coating. It is believed that vanadate ions, which are gradually dissolved by moisture entering from the outside, react with ions on the surface of the zinc-based plated steel sheet to form a passive film with good adhesion, protecting the exposed metal parts and exerting a rust-preventing effect.
[0122] The content of the vanadium compound in the primer coating is not particularly limited, but is preferably 4 to 20 mass% from the viewpoint of achieving both corrosion resistance and moisture resistance. If the content of the vanadium compound is less than 4 mass%, the inhibitor effect may decrease, leading to a decrease in corrosion resistance, whereas if the content of the vanadium compound is more than 20 mass%, the moisture resistance of the primer coating may decrease.
[0123] Phosphate compounds, which are one of the inorganic compounds, also act as inhibitors. Examples of the phosphate compounds include phosphoric acid, ammonium salts of phosphoric acid, alkali metal salts of phosphoric acid, and alkaline earth metal salts of phosphoric acid. In particular, alkali metal salts of phosphoric acid, such as calcium phosphate, are preferably used.
[0124] The content of the phosphate compound in the primer coating is not particularly limited, but is preferably 4 to 20 mass% from the viewpoint of achieving both corrosion resistance and moisture resistance. If the content of the phosphate compound is less than 4 mass%, the inhibitor effect may decrease, leading to a decrease in corrosion resistance, whereas if the content of the phosphate compound is more than 20 mass%, the moisture resistance of the primer coating may decrease.
[0125] Magnesium oxide, which is one of the inorganic compounds, produces a product containing Mg during initial corrosion, and as a sparingly soluble magnesium salt, it has the effect of stabilizing the material and improving corrosion resistance.
[0126] The content of the magnesium oxide in the primer coating is not particularly limited, but is preferably 4 to 20% by mass from the viewpoint of achieving both corrosion resistance and corrosion resistance of the processed part. If the content of the magnesium oxide is less than 4% by mass, the above effect may decrease, leading to a risk of a decrease in corrosion resistance, whereas if the content of the magnesium oxide is more than 20% by mass, the flexibility of the primer coating may decrease, leading to a decrease in the corrosion resistance of the processed part.
[0127] The primer coating film may also contain components other than the above-mentioned polyester resin having a urethane bond and inorganic compound. For example, a crosslinking agent used in forming a primer coating film can be mentioned. The crosslinking agent reacts with the polyester resin having the urethane bond to form a crosslinked coating film, and examples thereof include oxazoline compounds, epoxy compounds, melamine compounds, isocyanate compounds, carbodiimide compounds, silane coupling compounds, etc., and it is also possible to use two or more crosslinking agents in combination. Among them, from the viewpoint of the corrosion resistance of the processed part of the obtained coated steel plate, a blocked polyisocyanate compound or the like can be preferably used. Examples of the blocked polyisocyanate include those in which the isocyanate group of a polyisocyanate compound is blocked with, for example, alcohols such as butanol, oximes such as methyl ethyl ketoxime, lactams such as ε-caprolactams, diketones such as acetoacetic acid diester, imidazoles such as 2-ethylimidazole, or phenols such as m-cresol.
[0128] Furthermore, the primer coating film may contain various known components that are commonly used in the coating field, if necessary, such as various surface conditioners, such as leveling agents and defoamers, various additives, such as dispersants, anti-settling agents, ultraviolet absorbers, light stabilizers, silane coupling agents and titanate coupling agents, various pigments, such as coloring pigments and extender pigments, luster materials, curing catalysts, organic solvents, etc.
[0129] The thickness of the primer coating film is preferably 1.5 μm or more, because by making the thickness of the primer coating film 1.5 μm or more, it is possible to more reliably obtain the effect of improving corrosion resistance and the effect of improving adhesion with the chemical conversion coating film and the top coating film formed on the primer coating film.
[0130] The method for forming the primer coating film is not particularly limited. In addition, as for the method for applying the coating composition constituting the primer coating film, the coating composition can be preferably applied by a method such as roll coater coating or curtain flow coating. After applying the coating composition, the primer coating film can be obtained by baking the coating composition by a heating means such as hot air heating, infrared heating, or induction heating. The baking treatment is usually performed at a maximum plate temperature of about 180 to 270°C for about 30 seconds to 3 minutes in this temperature range.
[0131] In addition, with regard to the coating film constituting the coated steel plate of the present invention, it is preferable that a top coating film is further formed on the primer coating film. The topcoat coating film can impart beauty to the coated steel sheet, such as color, gloss, and surface condition, and can also improve various performance properties, such as processability, weather resistance, chemical resistance, stain resistance, water resistance, and corrosion resistance.
[0132] The configuration of the topcoat coating is not particularly limited, and the material, thickness, etc. can be appropriately selected depending on the required performance. For example, the topcoat film can be formed using a polyester resin paint, a silicon polyester resin paint, a polyurethane resin paint, an acrylic resin paint, a fluororesin paint, or the like. Furthermore, the topcoat coating film may contain appropriate amounts of titanium oxide, red iron oxide, mica, carbon black or other various coloring pigments; metallic pigments such as aluminum powder and mica; extender pigments consisting of carbonates, sulfates, etc.; various fine particles such as silica fine particles, nylon resin beads, acrylic resin beads, etc.; curing catalysts such as p-toluenesulfonic acid and dibutyltin dilaurate; wax; and other additives.
[0133] From the viewpoint of achieving both good appearance and workability, the thickness of the topcoat film is preferably 5 to 30 μm. When the thickness of the topcoat film is 5 μm or more, it is possible to more reliably stabilize the color appearance, and when the thickness of the topcoat film is 30 μm or less, it is possible to more reliably suppress the decrease in workability (the occurrence of cracks in the topcoat film).
[0134] The method of applying the coating composition for forming the topcoat coating film is not particularly limited. For example, the coating composition can be applied by a method such as roll coater coating or curtain flow coating. After applying the coating composition, the topcoat coating film can be formed by baking using a heating means such as hot air heating, infrared heating, or induction heating. The baking treatment is usually performed at a maximum plate temperature of about 180 to 270°C for about 30 seconds to 3 minutes in this temperature range.
[0135] The coated steel sheet of the present invention is characterized in that, like the surface of the hot-dip Al-Zn-Si-Mg-plated steel sheet of the present invention described above, the height difference of the steel sheet surface (coating surface) per mm length is 10 μm or less in an area excluding 50 mm from both ends of the steel sheet. When the height difference of the coating film surface is 10 μm or less, there are no wrinkle-like defects and an excellent surface appearance can be obtained. As described above, the wrinkle defects are defects in which the surface of the coating film is wrinkled and uneven due to Mg-based oxides, and appear as white streaks on the surface of the coating film. Therefore, suppressing the wrinkle defects means that the streaks are not visible. Therefore, by suppressing the height difference within a 1 mm long range of the steel sheet surface, i.e., the coating film surface, to within 10 μm, the streaks are not visible, and an excellent surface appearance can be obtained. From the same viewpoint, it is preferable that the height difference within a 1 mm long range of the steel sheet surface is within 5 μm. The steel sheet surface means the outermost surface of the steel sheet, and in the case of a coated steel sheet, means the coating surface. As for the method of obtaining the height difference within a range of 1 mm in length of the coating surface, the height difference within a range of 1 mm at any 100 points on the coated steel sheet can be obtained using a laser microscope, as in the case of the plating film surface described above, by calculating the average of the measured values.
[0136] The reason for controlling the height difference on the surface of the steel sheet in the range excluding 50 mm from both ends of the steel sheet is that, in general, it is difficult to control the coating weight at both ends of a hot-dip galvanized steel sheet compared to the center of the steel sheet, and the cooling rate is also different, so wrinkle-like defects are likely to occur. In addition, such both ends of the steel sheet are often trimmed before use, so there is almost no problem with the surface appearance.
[0137] As for the method of controlling the height difference of the coating surface to 10 μm or less per 1 mm of length of the steel sheet surface, it is important to suppress the height difference of the plating film surface as described above, and the height difference of the film surface can be suppressed by adjusting the Mg / Mn content ratio in the plating film or by performing other surface treatments for suppressing the height difference.
[0138] The method for producing a coated steel sheet of the present invention is a method for producing a coated steel sheet in which a coating film is formed on a plating film directly or via a chemical conversion film. In the manufacturing method of the present invention, the chemical conversion coating comprises a resin component containing 30 to 50 mass% in total of (a): an anionic polyurethane resin having an ester bond and (b): an epoxy resin having a bisphenol skeleton, the content ratio of (a):(b) being within a range of 3:97 to 60:40 by mass, and inorganic compounds including 2 to 10 mass% of a vanadium compound, 40 to 60 mass% of a zirconium compound, and 0.5 to 5 mass% of a fluorine compound; The coating film has at least a primer coating film, and the primer coating film contains a polyester resin having a urethane bond, and an inorganic compound containing a vanadium compound, a phosphoric acid compound, and magnesium oxide, The formation of the plating film includes a hot-dip galvanizing process in which the base steel sheet is immersed in a plating bath having a composition containing 45 to 65 mass% Al, 1.0 to 4.0 mass% Si, and 1.0 to 10.0 mass% Mg, with the balance being Zn and unavoidable impurities.
[0139] The conditions for the hot-dip galvanizing process are the same as those explained in the description of the hot-dip Al-Zn-Si-Mg-plated steel sheet of the present invention. EXAMPLES
[0140] [Example 1: Samples 1 to 28] A cold-rolled steel sheet having a thickness of 0.8 mm produced by conventional methods was used as the base steel sheet, and degreasing, annealing and plating processes were performed in a continuous hot-dip plating equipment to produce samples 1 to 28 of hot-dip Al-Zn-Si-Mg-plated steel sheets according to the conditions shown in Table 1. The composition of the plating bath used in the production of the hot-dip Al-Zn-Si-Mg-plated steel sheets was varied in the ranges of Al: 45-65 mass%, Si: 1.5-2.5 mass%, Mg: 1.0-4.5 mass%, Mn: 0.00-1.0 mass%, Sr: 0.00-1.0 mass%, B: 0.00-0.05 mass%, Ca: 0.00-1.0 mass%, Cr: 0.00-0.2 mass%, Ti: 0.00-0.2 mass%, and V: 0.00-0.2 mass% so as to obtain the composition of the plating film of each sample shown in Table 1. The bath temperature of the plating bath was 590°C in the case of Al: 45-55 mass%, and 630°C in the case of Al: 65 mass%, and was controlled so that the plating immersion sheet temperature of the base steel sheet was the same as the plating bath temperature. Furthermore, the plating process was carried out under conditions in which the sheet temperature was cooled to a temperature range of 520 to 500°C in 3 seconds. The coating weight of the plating film was 85±5 g / m per side for samples 1 to 23 and samples 27 to 28. 2 , Samples 24 to 26 are 50 to 125 g / m per side 2 It was controlled so that
[0141] <Evaluation> The following evaluations were carried out on each sample of the hot-dip Al-Zn-Si-Mg plated steel sheet obtained as described above. The evaluation results are shown in Table 1. (1) Structure of plating film (amount of coating, composition, X-ray diffraction intensity) After plating, a 100 mm diameter cut was made from each sample, the non-measurement surface was sealed with tape, and the plating was dissolved and removed using a mixture of hydrochloric acid and hexamethylenetetramine as specified in JIS H 0401: 2013. The adhesion weight of the plating film was calculated from the difference in the mass of the sample before and after removal. The calculated adhesion weight of the plating film is shown in Table 1. The stripper solution was then filtered, and the filtrate and solid content were analyzed. Specifically, the filtrate was analyzed by ICP atomic emission spectrometry to quantify the components other than insoluble Si. The solids were dried and incinerated in a 650°C heating furnace, and then melted by adding sodium carbonate and sodium tetraborate. The molten material was then dissolved in hydrochloric acid, and the solution was analyzed by ICP emission spectroscopy to quantify the insoluble silicon. The silicon concentration in the plating film was calculated by adding the soluble silicon concentration obtained by filtrate analysis to the insoluble silicon concentration obtained by solid content analysis. The composition of the plating film obtained as a result of calculation is shown in Table 1. Furthermore, each sample was sheared to a size of 100 mm x 100 mm, and the plating film on the surface to be evaluated was mechanically scraped off until the base steel sheet was revealed. The obtained powder was thoroughly mixed, and 0.3 g was taken out and a qualitative analysis of the above powder was performed using an X-ray diffraction apparatus (Rigaku Corporation, "SmartLab") under the following conditions: X-ray used: Cu-Kα (wavelength = 1.54178 Å), Kβ ray removal: Ni filter, tube voltage: 40 kV, tube current: 30 mA, scanning speed: 4° / min, sampling interval: 0.020°, divergence slit: 2 / 3°, solar slit: 5°, detector: high-speed one-dimensional detector (D / teX Ultra). The intensity obtained by subtracting the base intensity from each peak intensity was taken as the diffraction intensity (cps). The diffraction intensity of the Mg2Si (111) plane (planar spacing d = 0.3668 nm) and the diffraction intensity of the Si (111) plane (planar spacing d = 0.3135 nm) were measured.
[0142] (2) Surface appearance (2-1) Wrinkle defects The surface appearance of each sample of the obtained hot-dip Al-Zn-Si-Mg-plated steel sheet was visually inspected to confirm the occurrence of wrinkle-like defects. Furthermore, for each sample, 100 locations were randomly selected from the portion excluding 50 mm from both ends of the strip, and the height difference of the plating film surface in a 1 mm long range was measured using a laser microscope ("VK-X3000" manufactured by Keyence Corporation), and the average value was quantified as the surface shape. The occurrence state of wrinkle-like defects was evaluated according to the following criteria based on the occurrence of wrinkle-like defects and the surface shape. ◎: No wrinkle defects were observed (height difference is 5μm or less) ◯: No wrinkle defects were observed (height difference is 10 μm or less) ×: Wrinkle defects are observed (height difference exceeds 10 μm)
[0143] (2-2) Dross defects The surface appearance of each sample of the obtained hot-dip Al-Zn-Si-Mg plated steel sheet was visually inspected, and the presence or absence of dross defects was evaluated according to the following criteria. ○: No adhesion of granular dross is observed ×: Granular dross adhesion is observed
[0144] (3) Corrosion resistance evaluation Each sample of the obtained hot-dip Al-Zn-Si-Mg-plated steel sheet was sheared to a size of 120 mm x 120 mm, and then a range of 10 mm from each edge of the surface to be evaluated, as well as the end faces and the surface not to be evaluated, were sealed with tape to expose the surface to be evaluated in a size of 100 mm x 100 mm, which was used as a sample for evaluation. Three identical samples for evaluation were prepared. The three evaluation samples prepared as described above were all subjected to the Japanese Automotive Standard Combined Cyclic Test (JASO-CCT). The accelerated corrosion test started with wetting and continued for 300 cycles, after which the corrosion weight loss of each sample was measured using the methods specified in JIS Z 2383 and ISO 8407, and evaluated according to the following criteria. ◎: The corrosion loss of all three samples was 45g / m2 below ○: The corrosion loss of all three samples was 90 g / m 2 below ×: Corrosion loss of one or more samples is 90 g / m 2 Over
[0145] [Table 1]
[0146] The results in Table 1 show that the samples of the invention are superior in surface appearance to the samples of the comparative examples.
[0147] [Example 2: Samples 1 to 34] (1) A cold-rolled steel sheet having a thickness of 0.8 mm produced by a conventional method was used as a base steel sheet, and degreasing, annealing and plating treatments were performed in a continuous hot-dip plating facility to produce samples 1 to 34 of hot-dip Al-Zn-Si-Mg-plated steel sheets according to the conditions shown in Table 3. The composition of the plating bath used in the production of the hot-dip Al-Zn-Si-Mg-plated steel sheets was varied in the ranges of Al: 45-65 mass%, Si: 1.5-2.5 mass%, Mg: 1.0-4.5 mass%, Mn: 0.00-1.0 mass%, Sr: 0.00-0.00-1.0 mass%, B: 0.00-0.05 mass%, Ca: 0.00-1.0 mass%, Cr: 0.00-0.2 mass%, Ti: 0.00-0.2 mass%, and V: 0.00-0.2 mass%, so as to obtain the composition of the plating film of each sample shown in Table 3. The bath temperature of the plating bath was 590°C in the case of Al: 45-55 mass%, and 630°C in the case of Al: 65 mass%, and was controlled so that the plating immersion sheet temperature of the base steel sheet was the same as the plating bath temperature. Furthermore, the plating process was carried out under conditions in which the sheet temperature was cooled to a temperature range of 520 to 500°C in 3 seconds. The coating weight of the plating film was 85±5 g / m per side for samples 1 to 29 and samples 33 to 34. 2 , Samples 30 to 32 are 50 to 125 g / m per side 2 It was controlled so that
[0148] (2) Then, a chemical conversion coating was formed on the plating film of each sample of hot-dip Al-Zn-Si-Mg plated steel sheet using a bar coater, and the plated film was dried in a hot air oven (heating rate: 60°C / s, PMT: 120°C) to produce each sample of surface-treated steel sheet shown in Table 2. The chemical conversion treatment solutions were prepared by dissolving each component in water as a solvent to prepare surface treatment solutions A to F. The types of each component (resin, metal compound) contained in the surface treatment solutions are as follows. (resin) Urethane resin: Superflex 130, Superflex 126 (Dai-ichi Kogyo Seiyaku Co., Ltd.) Acrylic resin: Boncoat EC-740EF (DIC Corporation) (metal compound) P compound: Aluminum dihydrogen tripolyphosphate Silicon compounds: Silica V compound: Sodium metavanadate Mo Compounds: Molybdic Acid Zr compound: Potassium zirconyl carbonate The compositions of the prepared chemical conversion treatment solutions A to F and the adhesion weights of the formed chemical conversion coatings are shown in Table 1. The concentration of each component in Table 1 of this specification is the concentration (mass %) of the solid content.
[0149] [Table 2]
[0150] <Evaluation> The following evaluations were carried out on each sample of the surface-treated steel sheet obtained as described above. The evaluation results are shown in Table 3. (1) Structure of plating film (amount of coating, composition, X-ray diffraction intensity) After plating, a 100 mm diameter cut was made from each sample, the non-measurement surface was sealed with tape, and the plating was dissolved and removed using a mixture of hydrochloric acid and hexamethylenetetramine as specified in JIS H 0401: 2013. The adhesion weight of the plating film was calculated from the difference in the mass of the sample before and after removal. The calculated adhesion weight of the plating film is shown in Table 3. The stripper solution was then filtered, and the filtrate and solid content were analyzed. Specifically, the filtrate was analyzed by ICP atomic emission spectrometry to quantify the components other than insoluble Si. The solids were dried and incinerated in a 650°C heating furnace, and then melted by adding sodium carbonate and sodium tetraborate. The molten material was then dissolved in hydrochloric acid, and the solution was analyzed by ICP emission spectroscopy to quantify the insoluble silicon. The silicon concentration in the plating film was calculated by adding the soluble silicon concentration obtained by filtrate analysis to the insoluble silicon concentration obtained by solid content analysis. The composition of the plating film obtained as a result of calculation is shown in Table 3. Furthermore, each sample was sheared to a size of 100 mm x 100 mm, and the plating film on the surface to be evaluated was mechanically scraped off until the base steel sheet was revealed. The obtained powder was thoroughly mixed, and 0.3 g was taken out and a qualitative analysis of the above powder was performed using an X-ray diffraction apparatus (Rigaku Corporation, "SmartLab") under the following conditions: X-ray used: Cu-Kα (wavelength = 1.54178 Å), Kβ ray removal: Ni filter, tube voltage: 40 kV, tube current: 30 mA, scanning speed: 4° / min, sampling interval: 0.020°, divergence slit: 2 / 3°, solar slit: 5°, detector: high-speed one-dimensional detector (D / teX Ultra). The intensity obtained by subtracting the base intensity from each peak intensity was taken as the diffraction intensity (cps). The diffraction intensity of the Mg2Si (111) plane (plane spacing d = 0.3668 nm) and the diffraction intensity of the Si (111) plane (plane spacing d = 0.3135 nm) were measured. The measurement results are shown in Table 3.
[0151] (2) Surface appearance (2-1) Wrinkle defects The surface appearance of each sample of the obtained hot-dip Al-Zn-Si-Mg-plated steel sheet and surface-treated steel sheet was visually inspected to confirm the occurrence of wrinkle-like defects. Furthermore, for each sample, 100 locations were randomly selected from the portion excluding 50 mm from both ends of the strip, and the height difference of the plating film surface in a 1 mm long range was measured using a laser microscope ("VK-X3000" manufactured by Keyence Corporation), and the average value was quantified as the surface shape. The occurrence state of wrinkle-like defects was evaluated according to the following criteria based on the occurrence of wrinkle-like defects and the surface shape. ◎: No wrinkle defects were observed (height difference is 5μm or less) ◯: No wrinkle defects were observed (height difference is 10 μm or less) ×: Wrinkle defects are observed (height difference exceeds 10 μm)
[0152] (2-2) Dross defects The surface appearance of each sample of the obtained hot-dip Al-Zn-Si-Mg plated steel sheet was visually inspected, and the presence or absence of dross defects was evaluated according to the following criteria. ○: No adhesion of granular dross is observed ×: Granular dross adhesion is observed
[0153] (3) White rust resistance For each sample of hot-dip Al-Zn-Si-Mg plated steel sheet and surface-treated steel sheet, they were sheared to a size of 120 mm x 120 mm, and then a range of 10 mm from each edge of the surface to be evaluated, as well as the end faces and non-evaluation surfaces of the samples were sealed with tape to expose the surface to be evaluated in a size of 100 mm x 100 mm, and these were used as the samples for evaluation. Using the above evaluation samples, a salt spray test according to JIS Z 2371 was carried out for 90 hours and evaluated according to the following criteria. ◎: No white rust on the plate ○: White rust occurs on less than 10% of the flat surface area ×: White rust occurs on 10% or more of the flat plate area
[0154] (4) Corrosion resistance evaluation The obtained samples of the hot-dip Al-Zn-Si-Mg-plated steel sheet and the surface-treated steel sheet were sheared to a size of 120 mm x 120 mm, and the area of 10 mm from each edge of the surface to be evaluated, as well as the end faces and the surfaces not to be evaluated, were sealed with tape to expose the surface to be evaluated in a size of 100 mm x 100 mm, which was used as the sample for evaluation. Three identical samples for evaluation were prepared. The three evaluation samples prepared as described above were all subjected to the Japanese Automotive Standard Combined Cyclic Test (JASO-CCT). The accelerated corrosion test started with wetting and continued for 300 cycles, after which the corrosion weight loss of each sample was measured using the methods specified in JIS Z 2383 and ISO 8407, and evaluated according to the following criteria. ◎: The corrosion loss of all three samples was 30 g / m 2 below ○: The corrosion loss of all three samples was 70 g / m 2 below ×: Corrosion loss of one or more samples is 70 g / m 2 Over
[0155] [Table 3]
[0156] The results in Table 3 show that the samples of the invention are superior in surface appearance to the samples of the comparative examples.
[0157] [Example 3: Samples 1 to 37] (1) A cold-rolled steel sheet having a thickness of 0.8 mm produced by a conventional method was used as a base steel sheet, and degreasing, annealing and plating treatments were performed in a continuous hot-dip plating facility to produce samples 1 to 37 of hot-dip Al-Zn-Si-Mg-plated steel sheets according to the conditions shown in Table 5. The composition of the plating bath used in the production of the hot-dip Al-Zn-Si-Mg-plated steel sheets was varied in the ranges of Al: 45-65 mass%, Si: 1.5-2.5 mass%, Mg: 1.0-4.5 mass%, Mn: 0.00-1.0 mass%, Sr: 0.00-1.0 mass%, B: 0.00-0.05 mass%, Ca: 0.00-1.0 mass%, Cr: 0.00-0.2 mass%, Ti: 0.00-0.2 mass%, and V: 0.00-0.2 mass% so as to obtain the composition of the plating film of each sample shown in Table 5. The bath temperature of the plating bath was 590°C in the case of Al: 45-55 mass%, and 630°C in the case of Al: 65 mass%, and was controlled so that the plating immersion sheet temperature of the base steel sheet was the same as the plating bath temperature. Furthermore, the plating process was carried out under conditions in which the sheet temperature was cooled to a temperature range of 520 to 500°C in 3 seconds. The coating weight of the plating film was 85±5 g / m per side for samples 1 to 32 and samples 36 to 37. 2 , Samples 33 to 35 are 50 to 125 g / m per side 2 It was controlled so that
[0158] (2) After that, the coating of each sample of hot-dip galvanized steel sheet prepared was coated with the chemical conversion treatment solution shown in Table 4 using a bar coater, and then dried in a hot air drying furnace (achieved sheet temperature: 90°C) to obtain a coating weight of 0.1 g / m 2 A chemical conversion coating was formed. The chemical conversion treatment liquid used was prepared by dissolving each component in water as a solvent, and had a pH of 8 to 10. The types of each component (resin component, inorganic compound) contained in the chemical conversion treatment liquid are as follows: (Resin component) Resin A: (a) an anionic polyurethane resin having an ester bond (Superflex 210 manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and (b) an epoxy resin having a bisphenol skeleton (Yukarejin RE-1050 manufactured by Yoshimura Oil Chemical Co., Ltd.) mixed in a mass ratio of (a):(b) = 50:50. Resin B: Acrylic resin (DIC Corporation "Boncoat EC-740EF") (Inorganic compound) Vanadium compounds: Organic vanadium compounds chelated with acetylacetone. Zirconium Compounds: Ammonium Zirconium Carbonate Fluorine compounds: Ammonium fluoride
[0159] (3) Then, a primer paint was applied onto the chemical conversion coating film formed as described above using a bar coater, and baking was performed under conditions of a steel plate temperature of 230°C and a baking time of 35 seconds, thereby forming a primer coating film having the component composition shown in Table 4. Thereafter, a topcoat paint composition was applied onto the primer coating film formed as described above using a bar coater, and baking was performed under conditions of a steel plate temperature of 230°C to 260°C and a baking time of 40 seconds, thereby forming a topcoat coating film having the resin conditions and film thickness shown in Table 4, and each sample coated steel plate was produced. The primer coating was obtained by mixing the components and then stirring for about 1 hour in a ball mill. The following resin components and inorganic compounds were used to compose the primer coating film. (Resin component) Resin α: A urethane-modified polyester resin (obtained by reacting 455 parts by mass of polyester resin and 45 parts by mass of isophorone diisocyanate, having a resin acid value of 3, a number average molecular weight of 5,600, and a hydroxyl value of 36) cured with a blocked isocyanate was used. The polyester resin to be urethane-modified was prepared under the following conditions: 320 parts by mass of isophthalic acid, 200 parts by mass of adipic acid, 60 parts by mass of trimethylolpropane, and 420 parts by mass of cyclohexanedimethanenol were charged into a flask equipped with a stirrer, a distillation column, a water separator, a cooling tube, and a thermometer, and the mixture was heated and stirred, and the temperature was raised from 160°C to 230°C at a constant rate over 4 hours while distilling off the generated condensed water outside the system. After the temperature reached 230°C, 20 parts by mass of xylene was gradually added, and the condensation reaction was continued while maintaining the temperature at 230°C. The reaction was terminated when the acid value became 5 or less, and the mixture was cooled to 100°C, and then 120 parts by mass of Solvesso 100 (trade name, high-boiling aromatic hydrocarbon solvent, manufactured by Exxon Mobil Corp.) and 100 parts by mass of butyl cellosolve were added to obtain a polyester resin solution. Resin β: urethane-cured polyester resin ("Evaclad 4900" manufactured by Kansai Paint Co., Ltd.) (Inorganic compound) Vanadium Compounds: Magnesium Vanadate Phosphate Compounds: Calcium Phosphate Magnesium oxide compounds: Magnesium oxide In addition, the resins used in the topcoat coating shown in Table 4 were the following paints. Resin I: Melamine-cured polyester paint (BASF Japan Ltd. "Precolor HD0030HR") Resin II: Organosol-based baking-type fluororesin paint with a mass ratio of polyvinylidene fluoride and acrylic resin of 80:20 (BASF Japan Ltd. "Precolor No. 8800HR")
[0160] [Table 4]
[0161] <Evaluation> The following evaluations were carried out on each of the coated steel sheet samples obtained as described above. The evaluation results are shown in Table 5. (1) Structure of plating film (amount of coating, composition, X-ray diffraction intensity) After plating, a 100 mm diameter cut was made from each sample, the non-measurement surface was sealed with tape, and the plating was dissolved and removed using a mixture of hydrochloric acid and hexamethylenetetramine as specified in JIS H 0401: 2013. The adhesion weight of the plating film was calculated from the difference in the mass of the sample before and after removal. The calculated adhesion weights of the plating film are shown in Table 5. The stripper solution was then filtered, and the filtrate and solid content were analyzed. Specifically, the filtrate was analyzed by ICP atomic emission spectrometry to quantify the components other than insoluble Si. The solids were dried and incinerated in a 650°C heating furnace, and then melted by adding sodium carbonate and sodium tetraborate. The molten material was then dissolved in hydrochloric acid, and the solution was analyzed by ICP emission spectroscopy to quantify the insoluble silicon. The silicon concentration in the plating film was calculated by adding the soluble silicon concentration obtained by filtrate analysis to the insoluble silicon concentration obtained by solid content analysis. The composition of the plating film obtained as a result of calculation is shown in Table 5. Furthermore, each sample was sheared to a size of 100 mm x 100 mm, and the plating film on the surface to be evaluated was mechanically scraped off until the base steel sheet was revealed. The obtained powder was thoroughly mixed, and 0.3 g was taken out and a qualitative analysis of the above powder was performed using an X-ray diffraction apparatus (Rigaku Corporation, "SmartLab") under the following conditions: X-ray used: Cu-Kα (wavelength = 1.54178 Å), Kβ ray removal: Ni filter, tube voltage: 40 kV, tube current: 30 mA, scanning speed: 4° / min, sampling interval: 0.020°, divergence slit: 2 / 3°, solar slit: 5°, detector: high-speed one-dimensional detector (D / teX Ultra). The intensity obtained by subtracting the base intensity from each peak intensity was taken as the diffraction intensity (cps). The diffraction intensity of the Mg2Si (111) plane (planar spacing d = 0.3668 nm) and the diffraction intensity of the Si (111) plane (planar spacing d = 0.3135 nm) were measured.
[0162] (2) Surface appearance (2-1) Wrinkle defects The surface appearance of each of the obtained coated steel sheet samples was visually inspected to confirm the presence or absence of wrinkle-like defects. Furthermore, for each sample, 100 locations were randomly selected from the area excluding 50 mm from both ends of the strip, and the height difference of the plating film surface within a 1 mm long range was measured using a laser microscope (Keyence Corporation, "VK-X3000"), and the average value was quantified as the surface shape. The occurrence state of wrinkle-like defects was evaluated according to the following criteria based on the occurrence or absence of wrinkle-like defects and the surface shape. ◎: No wrinkle defects were observed (height difference is 5μm or less) ◯: No wrinkle defects were observed (height difference is 10 μm or less) ×: Wrinkle defects are observed (height difference exceeds 10 μm)
[0163] (2-2) Dross defects The surface appearance of each of the obtained coated steel sheet samples was visually inspected, and the presence or absence of dross defects was evaluated according to the following criteria. ○: No adhesion of granular dross is observed ×: Granular dross adhesion is observed
[0164] (3) Corrosion resistance evaluation Each sample of the obtained coated steel plate was sheared to a size of 120 mm x 120 mm, and then 10 mm from the edge of three of the four sides of the evaluation surface, as well as the end surface and the non-target surface, were sealed with tape, and only one edge was not sealed with tape, leaving the sheared end surface exposed, and this was used as the evaluation sample. Note that the shearing was performed so that the burr on the sheared end surface faced the evaluation surface. The above evaluation samples were used to carry out the Japanese Automotive Standard Combined Cyclic Test (JASO-CCT). The accelerated corrosion test started with wetting, and samples were taken out every 20 cycles, washed with water, dried, and then visually inspected. The number of cycles at which red rust was confirmed on the sheared edge of one side that was not sealed with tape was evaluated according to the following criteria. ◎: Number of cycles in which red rust occurred on three samples ≥ 600 cycles ○: Number of cycles in which red rust occurred on 3 samples ≥ 400 cycles ×: Number of cycles in which red rust occurs on one or more samples < 400 cycles
[0165] [Table 5]
[0166] The results in Table 5 show that the samples of the invention are superior in both surface appearance and corrosion resistance to the samples of the comparative examples. [Industrial Applicability]
[0167] According to the present invention, it is possible to provide a hot-dip Al-Zn-Si-Mg-plated steel sheet which is free from other defects such as dross defects, suppresses the occurrence of wrinkle-like defects, and has an excellent surface appearance. Furthermore, according to the present invention, it is possible to provide a surface-treated steel sheet having an excellent surface appearance and white rust resistance, and a coated steel sheet having an excellent surface appearance and excellent corrosion resistance.
Claims
1. A hot-dip Al-Zn-Si-Mg-based plated steel sheet having a plating film, The plating film has a composition containing 45 to 65 mass% Al, 1.0 to 3.0 mass% Si, 1.0 to 10.0 mass% Mg, and 0.01 to 0.5 mass% Mn, with the remainder being Zn and unavoidable impurities; A hot-dip Al-Zn-Si-Mg plated steel sheet, characterized in that the height difference of the steel sheet surface per mm of length is 10 μm or less in an area excluding 50 mm from both ends of the steel sheet.
2. 2. The hot-dip Al-Zn-Si-Mg plated steel sheet according to claim 1, characterized in that the plating film has a Mn content of 0.1 to 0.3 mass %.
3. 3. The hot-dip Al-Zn-Si-Mg plated steel sheet according to claim 1, further comprising an alloy layer containing Mn at an interface between the plated film and a base steel sheet.
4. The hot-dip Al-Zn-Si-Mg plated steel sheet according to any one of claims 1 to 3, characterized in that the plating film further contains 0.01 to 3.0 mass% in total of one or more elements selected from B, Ca, Ti, V, Cr, Sr, Mo, In, Sn, Sb, Ce, and Bi.
5. A surface-treated steel sheet comprising the plating film according to any one of claims 1 to 4 and a chemical conversion film formed on the plating film, The chemical conversion coating film is a surface-treated steel sheet characterized in that it contains at least one resin selected from the group consisting of epoxy resins, urethane resins, acrylic resins, acrylic silicone resins, alkyd resins, polyester resins, polyalkylene resins, amino resins, and fluororesins, and at least one metal compound selected from the group consisting of P compounds, Si compounds, Co compounds, Ni compounds, Zn compounds, Al compounds, Mg compounds, V compounds, Mo compounds, Zr compounds, Ti compounds, and Ca compounds.
6. A coated steel sheet having a coating film formed directly or via a chemical conversion coating on the plating film according to any one of claims 1 to 4, The chemical conversion coating contains a resin component that contains 30 to 50 mass% in total of (a): an anionic polyurethane resin having an ester bond and (b): an epoxy resin having a bisphenol skeleton, the content ratio of (a) to (b) ((a):(b)) being in the range of 3:97 to 60:40 in terms of mass ratio, and an inorganic compound that contains 2 to 10 mass% of a vanadium compound, 40 to 60 mass% of a zirconium compound, and 0.5 to 5 mass% of a fluorine compound; The coating film has at least a primer coating film, and the primer coating film contains a polyester resin having a urethane bond, and an inorganic compound including a vanadium compound, a phosphate compound, and magnesium oxide.
Citation Information
Patent Citations
Hot-press member and method for producing the same
JP2020143354A
Zinc-based plated steel sheet
JP2021181630A
HOD DIPPED Al-Zn-Si-Mg COATED STEEL SHEET AND METHOD FOR PRODUCING SAME, SURFACE-TREATED STEEL SHEET AND METHOD FOR PRODUCING SAME, AND COATED STEEL SHEET AND METHOD FOR PRODUCING SAME
WO2023132327A1
JP1975000039A
JP1975020228A